In-Situ engineering of hierarchical ZIF@HOF heterostructures for efficient antibiotic degradation: Mechanistic insights from experimental and DFT studies - Ali Ahmad; Naeem Akram; Muhammad Khurram Tufail; Bing Yu; Hailin Cong (Water Research, 2027)

Multivariate analysis highlights genetic structure in Olive (Olea Europaea L.) germplasm using Resource-Efficient RAPD marker system - Ayesha Wadood; Amjad Hameed; Muhammad Yussouf Saleem; Abdul Rehman Khan; Saba Akram (Molecular Biology Reports, 2026)

Transgene-free plant genome editing via viral delivery of miniature CRISPR-Cas12f - Muhammad Jawad Akbar Awan; Afzal Akram; Rubab Zahra Naqvi; Mariam Akhtar; Saqib Siddique; Muhammad Ismail Buzdar; Imran Amin; Shahid Mansoor (Functional & Integrative Genomics, 2026)

Strait of Hormuz disruption, geopolitical dispute intensity and Brent-based hedging effectiveness in European fuel markets: Empirical evidence from DCC-GARCH approach - Hafiz Muhammad Naveed; Huaping Sun; Muhammad Shahid; Rabia Akram; Zaiba Ali (Energy Policy, 2026)

FruScab-E3Net: A Deep Learning Ensemble Framework for Scab Disease Detection and Classification in Fruits - Tamoor Khan; Sheeraz Akram; Arfan Jaffar; Muhammad Shahid Iqbal; Rashid Abbasi (Applied Fruit Science, 2026)

A hybrid deep learning–ensemble model for accurate and explainable electricity demand forecasting in renewable energy communities - Muhammad Akram; Chiara Martone; Giovanna Pallotta; Maurizio Sasso; Riccardo Amatore (Energy and Buildings, 2026)

Nanopesticides in sustainable agriculture: multi-pathogen control, environmental impact, and intelligent delivery systems - Muhammad Abu Bakar Saddique; Yitao Xi; Munazzah Ijaz; Sawera Akram; Shihang Wang; Zhiwei Zhang; Xinyi Yang; Rana Zain Abbas; Maozhi Ren; Xiumei Luo (Bioresource Technology, 2026)

Adaptive strategies of Tamarix aphylla in hyper-saline conditions of Cholistan Desert - Muhammad Akram; Nargis Naz; Hafiz Muhammad Mohsin Hassan; Maqbool Ahmed; Leman Aliyeva; Muhammad Yousaf Nadeem; Hind Saad Alsubaie; Sahar Anwar Almalki; Abdelrahman R. Ahmed; Abdullah R. Alanzi (The Science of Nature, 2026)

Development and Characterization of Proliposomes for Sustained Oral Delivery of the DPP-4 Inhibitor Vildagliptin - Shazia Ashraf; Asadullah Madni; Faizan Akram; Muhammad Farhan Hanif; Afifa Shafiq; Iqra Fatima Ayub (Journal of Pharmaceutical Innovation, 2026)

Rationalizing bud load for grapevine cv sugraone for balanced yield and superior fruit quality in a warm semi-arid region - Muhammad Hashir Khan; Irfan Ali; Muhammad Tahir Akram; Mahmood-ul-Hassan; Adeel Anwar; Rizwan Rafique (Acta Physiologiae Plantarum, 2026)

Retraction notice to “The asymmetric nexus between air pollution and COVID-19: Evidence from a non-linear panel autoregressive distributed lag model” [Environ. Res. 209 (2022) 112848] - Chen Wen; Rabia Akram; Muhammad Irfan; Wasim Iqbal; Vishal Dagar; Ángel Acevedo-Duqued; Hayot Berk Saydaliev (Environmental Research, 2026)

A Fibrous Thin Film Based on Silver(I) Metal–Organic Framework/Polyethersulfone Composite with Excellent Antibacterial Properties and Photocatalytic Degradation of Methylene Blue - Humaira Shaheen; Abdul Rauf; Muhammad Arif; Muhammad Akram; Komal Aroosh; Mehdi Hassan; Muhammad Jahangir (Water, Air, & Soil Pollution, 2026)

A framework for multi-target temperature profile generation using functional PCA and Gaussian mixture models for Fire PRA - Akram S. Batikh; Yahya A. Alzahrani; Muhammad S. Battikh; Rawan Mustafa; Mihai A. Diaconeasa (Annals of Nuclear Energy, 2026)

Retraction notice to “Variations and driving factors of leaf functional traits in the dominant desert plant species along an environmental gradient in the drylands of China” [Sci. Total Environ. 897 (2023) 165394] - Muhammad Adnan Akram; Xiaoting Wang; Nawal Shrestha; Yahui Zhang; Ying Sun; Shuran Yao; Jinhui Li; Qingqing Hou; Weigang Hu; Jinzhi Ran; Jianming Deng (Science of The Total Environment, 2026)

Unlocking hybrid electrokinetic opportunities for soils restoration and addressing current challenges - Muhammad Imran; Kainat Anwer; Samiullah Akram; Nageen Kousar; Abdul Ahad Hussain; Jinsheng Zhao; Limin Wang (Process Safety and Environmental Protection, 2026)

Integrating alternate wetting‑drying irrigation and root‑zone nitrogen management enhances rice productivity and environmental sustainability - Bin Wang; Solomon Yokamo; Muhammad Ahmed Akram; Yiliu Wang; Muhammad Irfan; Xinyuan Lu; Yifan Wang; Yujie Zha; Xiaoqin Chen; Dianjun Lu; Huoyan Wang (Field Crops Research, 2026)

Deciphering the role of potato peel on sunflower hybrids growth, photosynthesis, osmoregulation, oxidative defense and ion uptake under salinity - Sundas Fatima; Aasma Tufail; Muhammad Bilal Hafeez; Samreen Nazeer; Noreen Zahra; Fatima Latif; Sabina Asghar; Muhammad Ahsan; Muhammad Hamza; Muhammad Zubair Akram (Biocatalysis and Agricultural Biotechnology, 2026)

Analyzing Household Biological Waste for Energy Efficiency: Advancement Towards Sustainable Energy - Dhaif Allah Ahmed Hadi; Jicheng Liu; Javed Akram; Shahid Ali; Song Yanan; Kathih Ahmed Ali Hadi; Muhammad Sajjad Hussain (Circular Economy and Sustainability, 2026)

Molecular evidence of two begomoviruses and a novel DNA-B infecting Duranta erecta variegata in Pakistan - Afzal Akram; Mahnoor Jamil; Imran Amin; Jodi A. Scheffler; Brian E. Scheffler; Muhammad Saeed; Shahid Mansoor (Virus Genes, 2026)

Nanoparticles in potato disease management: Applications, mechanisms, and future perspectives for sustainable crop production - Aneeza Ishfaq; Ishrat Bano; Irfan Haidri; Muhammad Shahid; Muhammad Sohail Akram; Muhammad Khubeb Ashfaq; Sabir Hussain; Tanvir Shahzad; Faisal Mahmood (Physiological and Molecular Plant Pathology, 2026)

From barns to atmosphere: Pakistan's livestock manure-derived NH3, N2O, and CH4 emissions (1961–2022) and cleaner production pathways - Syed Qasim Ali Shah; Noor Haleem; Chaudary Muhammad Haris; Leena Khan; Yousuf Jamal; Humayoun Akram; Xufei Yang (Journal of Cleaner Production, 2026)

The effects of vitamin D supplementation on inflammatory biomarkers: an umbrella study of meta-analysis on randomized controlled trials - Chou-Yi Hsu; Hassan Youssef Hussein; Karam Akram Al-akkam; Tushar B. Gajjar; Hamad AlMohamadi; Nodir Khonturaev; Sandeep Kumar Shukla; Safa Hussien Radhi; Aseel Smerat; Muhammad Shahid Iqbal (Inflammopharmacology, 2026)

Advances in Coated Fertilizers for Sustainable Agriculture - Muhammad Tahir Murad; Sadia Murad; Waqar Akram; Mohammad Shafiq u Rahman; Afroz Rais; Abdul Qadir; Dawood Atta (Journal of Soil Science and Plant Nutrition, 2026)

Unlocking ketone dimerization efficiency with multifunctional Zr and Hf based UiO-66 and NUS-6 MOFs: A synergy of experiment and theory - Muhammad Kashif Majeed; Rashid Iqbal; M.Umar Majeed; Muhammad Akram; M.Zeeshan Ashfaq; Adil Saleem (Fuel, 2026)

Titanium dioxide nanoparticles as a sustainable strategy to control root-knot nematodes (RKNs) in tomato (Solanum lycopersicum L.) - Asma Mehak; Abida Akram; Amjad Ali; Naveed Iqbal Raja; Tariq Mukhtar; Jaya Seelan Sathiya Seelan; Muhammad Shahbaz (Physiological and Molecular Plant Pathology, 2026)

Achieving co-benefits in enhancing rice productivity and mitigating the eco-environmental impacts through root zone precision nitrogen management in large-scale farms - Bin Wang; Solomon Yokamo; Muhammad Ahmed Akram; Xiaoqin Chen; Yiliu Wang; Muhammad Irfan; Xinyuan Lu; Yujie Zha; Dianjun Lu; Huoyan Wang (Field Crops Research, 2026)

Unveiling Morpho-Anatomical Strategies of Cenchrus Ciliaris L. for Survival under Vehicular Pollution Stress - Hafiz Muhammad Mohsin Hassan; Muhammad Akram; Imran Haider; Muhammad Altaf Nazir; Lamy Hamed; Abdullateef Al-Saeed; ElSayed A. Badr; Ahmed Ismail (Water, Air, & Soil Pollution, 2026)

Retraction Note: Study of variability, combining ability, genetics and association of different yield related traits in rice (Oryza sativa L.) genotypes - Zeeshan Ali; Muhammad Naeem; Iqra Rafiq; Rao Muhammad Ikram; M. Irfan Akram; Ehab I. Taha; Mounir M. Bekhit; Ozhan Simsek; Tolga Izgu; Temoor Ahmed; Javed Iqbal; Rashid Iqbal (Genetic Resources and Crop Evolution, 2026)

Spawning and developmental biology of vulnerable catfish, Wallago attu : Implications for quality seed production and stock replenishment - Saeed Akram Khan; Muhammad Khalil Ahmad Khan; Shahid Sherzada (Journal of Fish Biology, 2026)
Freshwater catfish, Wallago attu , is a popular fish species due to its excellent taste and low quantity of intramuscular bones. Scientific and evidence‐based studies on the embryonic and larval development of this vulnerable fish species are limited. We attempted artificial breeding using Ovaprim, and photographs of the embryological events were taken, revealing each stage of early development. For this, a sequence of microscopic analysis was performed using a trinocular digital microscope. Time‐lapse imaging was also performed to calculate the duration of each developmental stage. The eggs were spherical, and highly adhesive, with a diameter of 1.74 ± 0.11 in T1 and T2, 1.86 ± 0.17 and 1.8 ± 0.16 in T3 and T4, respectively. Hatching occurred at 979.33 ± 5.13, 973 ± 21.07, 981.67 ± 11.93 and 969 ± 7.21 min post‐fertilization (mpf) in T1, T2, T3 and T4, respectively. During embryonic development, the blastodisc appeared at 55.33 ± 4.04 (T1), 54.67 ± 5.13 (T2), 58.33 ± 3.79 (T3) and 58.33 ± 3.51 (T4). First cleavage appeared at 64.33 ± 2.08 (T1), 63.67 ± 5.03 (T2), 68 ± 1 (T3) and 66 ± 4.36 (T4) mpf, resulting in two equal blastomeres. Embryonic body movements started at 652 mpf. Free body embryonic development (ranging from the two‐cell to the pre‐hatching stage) took 810 mpf. Hatching occurred at 979.33 ± 5.13 (T1), 973 ± 21.07 (T2), 981.67 ± 11.93(T3) and 969 ± 7.21(T4) mpf, with average larval lengths of 4.88 ± 0.19 (T1), 5 ± 0.16 (T2), 4.88 ± 0.19 (T3) and 4.88 ± 0.28 (T4) mm. Such information will have significant implications on conservation and sustainable seed production of this species. The findings of this study will contribute to the advancement of W. attu aquaculture by providing valuable insights into quality seed production and stock replenishment.

Biofloc technology: a comprehensive review of its implications for enhancing aquaculture production - Nadia Yasin; Syed Makhdoom Hussain; Bedur Faleh Albalawi; Muhammad Amjad; Adan Naeem; Eman Naeem; Zainab Akram; Mubeena Akbar (Aquaculture International, 2026)

A comprehensive review on microplastics: Their presence in surface and ground water, environmental distribution, and impact on human and aquatic systems - Khashia Rashid; Shaukat Ali; Asif Hanif Chaudhry; Nosheen Sial; Muhammad Rizwan Akram; Muhammad Aslam (Science of The Total Environment, 2026)

Dynamics of the boundary layer assumption for mixed convection nanofluid flow over a parabolic surface - T. Salahuddin; Ahitsham Akram; Muhammad Awais; Mair Khan; Eatedal Alabdulkreem; Farkhod Rakhmonov (Dynamics of Atmospheres and Oceans, 2026)

Interactive effects of incubation and post-hatch lighting schedules on blood biochemistry and meat quality characteristics in Japanese quail - Hussnain Ali Akram; Jibran Hussain; Sohail Ahmad; Muhammad Hayat Jaspal (Tropical Animal Health and Production, 2026)

Microencapsulation of Probiotics in Polymeric Microgels: Enhanced Viability and Stability through Inorganic Nanoparticle Doping - Muhammad Umar Farooq; Ashok Kumar Bishoyi; Nameer khairullah Mohammed; Suhas Ballal; Abhayveer Singh; Supriya S.; Faiyaz Ahmed; Laraib Shoukat; Noor Akram; Fakhar Islam (Probiotics and Antimicrobial Proteins, 2026)

The Potential Efficiency of Plant growth-promoting Rhizobacteria and Zinc Oxide Nanoparticles in Enhancing Pakchoi Tolerance to Lead Stress - Shoaib Ahmad; Abdul Ghafoor; Azeem Ahmad; Sarah Owdah Alomrani; Ahmad F. Alhomodi; Hamid Ullah; Tahira Akram; Lin Jianyu; Muhammad Ali Alshehri; Shafaqat Ali (Journal of Soil Science and Plant Nutrition, 2026)

Integrating phenotypic, antioxidant, and molecular analyses to identify drought-tolerant wheat genotypes for climate resilience and genetic improvement - Hafiz Ghulam Muhu Din Ahmed; Tao Yang; Mueen Alam Khan; Muhammad Irfan Akram; Rashid Iqbal; Sajid Hussain; Muhammad Danial Shafiq; Mohamed El-Zaidy; Islem Abid (Cereal Research Communications, 2026)

Leucocoprinus aurantiopileus (Agaricaceae), a New Species from Pakistan - Fazli Maula; Malka Saba; Muhammad Asif; Afifa Kainat Rani; Wajahat Akram; Fahim Ullah; Saher Batool; Kainat Bakhsh; Ayesha Bibi; Aiman Izhar; Najam Ul Sehar Afshan; Abdul Nasir Khalid (New Zealand Journal of Botany, 2026)
A novel species, Leucocoprinus aurantiopileus , is described from Margalla Hills National Park, Islamabad, Pakistan, using an integrated approach. Phylogenetic analyses based on combined internal transcribed spacer and large subunit sequences confirm its placement within Leucocoprinus . L. aurantiopileus is distinguished by a conical to campanulate, subumbonate to umbonate pileus, dark red center, and light orange margins, along with subcylindrical to oblong basidiospores. We provide detailed descriptions, colored photographs, microscopic structures, and a phylogenetic tree. This discovery highlights the mycological diversity of Margalla Hills and emphasizes the need for further fungal exploration in the region.

Coprinellus gregariodiguttulatus , a New Coprinoid Species from Margalla Hills, Islamabad, Pakistan - Fahim Ullah; Malka Saba; Iram Fatima; Muhammad Asif; Mohsin Ullah; Fazli Maula; Wajahat Akram; Amir Sohail (New Zealand Journal of Botany, 2026)
Coprinellus gregariodiguttulatus is described as a new species from Quaid‐i‐Azam University, Islamabad, Pakistan, based on morphological and molecular analyses. The species is distinguished by its small gray to light gray basidiomata, paraboloid to hemispherical pileus, and oblong to obovoid or rarely lemon basidiospores. Phylogenetic analysis of the internal transcribed spacer (ITS) region supports its placement within Coprinellus sect. Disseminati is a distinct lineage, closely related to but separate from other known taxa. This discovery from an underexplored region highlights the potential for uncovering further novel fungal diversity in Pakistan.

Experimental and computational evaluation of dinaphthodiospyrol F and dinaphthodiospyrol G from Diospyros lotus L. as ectonucleotide pyrophosphatase/phosphodiesterase 1 (ENPP1) inhibitors - Abdur Rauf; Yahya S. Al-Awthan; Omar S. Bahattab; Muhammad Saleem; Zuneera Akram; Giovanni Ribaudo (Natural Product Research, 2026)

Pilot-scale demonstration and practical challenges of bioenergy with CCS (BECCS) using rotating packed bed - Muhammad Akram; Kris Milkowski; Abdulaziz Gheit; Janos Szuhanszki; Ihab Ahmed; Jon Lee; Mohamed Pourkashanian (Fuel, 2026)

Hyperbranched aromatic polyamide-modified nanofiltration membranes for improved water permeability and salt rejection - Muhammad Adnan Akram; Shengchao Zhao; Mengting Wang; Munir Hussain; Q. Jason Niu (Desalination, 2026)

Adaptive morphological and physiological strategies of Sporobolus ioclados in desert ecosystem - Muhammad Akram; Nargis Naz; Ummar Iqbal; Syeda Refat Sultana; Fahim Arshad; Muhammad Waheed; Muhammad Adeel Ghafar; Hafiz Muhammad Mohsin Hassan; Arslan Asghar; Abeer Hashem; Dalal Saad Alharbi; Graciela Dolores Avila-Quezada; et al. (The Science of Nature, 2026)

Impact of Egyptian grass (Dactyloctenium aegyptium) competition on performance of fine and coarse rice under dry direct-seeded aerobic systems - Muhammad Nawaz; Abdul Khaliq; Saddam Hussain; Ghulam Murtaza; Hafiz Muhammad Akram (Phytoparasitica, 2026)

Green Synthesis of a Reversible “ON-OFF-ON” Fluorescent Sensor for Fe3+ using Licorice-Derived N-Doped Carbon Dots - Zubair Akram; Anam Arshad; Mohsin Tehseen; Muhammad Mehdi; Ali Raza; Yulan Shi; Nan Wang; Sajida Noureen; Feng Yu (Journal of Fluorescence, 2026)

First record of Micropsalliota (Agaricaceae) from Pakistan with two novel species - Fazli Maula; Malka Saba; Wajahat Akram; Muhammad Asif (New Zealand Journal of Botany, 2025)

Morphology and phylogeny reveal four new species and a new record of Volvariella from southern Punjab, Pakistan - Muhammad Asif; Malka Saba; Fazli Maula; Wajahat Akram; Abdul Rehman Niazi; Qudsia Firdous; Irmgard Krisai-Greilhuber; Mubashar Raza (New Zealand Journal of Botany, 2025)

Alleviating stocking density stress in juvenile rainbow trout (Oncorhynchus mykiss) through dietary nano-selenium: Effects on growth, antioxidant activity, and immune response - Mashooq Ali; Aqsa Akram; Farid Ahmad Jan; Aziz Ahmad; Ashiq Hussain; Fahim Ullah Khan; Muhammad Arshad (Journal of Trace Elements in Medicine and Biology, 2025)

A novel hybrid MOF–metal oxide electrochemical sensor for ultra-trace detection of cadmium ions - Sabah Haider; Mujahid Mustaqeem; Maria Zaib; Mohammed Ashraf Gondal; Umar Farooq; Muhammad Salman; Rabia Akram Bajwa (Journal of Environmental Chemical Engineering, 2025)

High accuracy computational approach to study Casson hybrid nanofluid flow under induced magnetic field inside wavy walls configuration having peristaltic motion with entropy generation - Noreen Sher Akbar; Javaria Akram; S. Ijaz; Zaib Jahan; Taseer Muhammad; Muhammad Bilal Habib; M. Fiaz Hussain; M. Farooq (Dynamics of Atmospheres and Oceans, 2025)

Beta-Glucan in barley as a natural immunomodulator: mechanisms and therapeutic potential - Hafiz Ghulam Muhu Din Ahmed; Li’E Yang; Xiaomeng Yang; Jiazhen Yang; Sajid Hussain; Muhammad Danial Shafiq; Muhammad Irfan Akram; Muhammad Sajad; Yawen Zeng (Molecular Biology Reports, 2025)

Evaluation of Agronomic Traits and Bioactive Compounds in Five Mentha Species Under Soil-Based and Hydroponic System - Muhammad Azam Khan; Ismara Naseem; Muhammad Tahir Akram; Umer Habib; Rashid Mehmood Rana (Journal of Soil Science and Plant Nutrition, 2025)

Acid-Modified Biochar Mitigates Salt Stress in Maize by Enhancing Nutrient Availability and Antioxidant Defense System Under Variable Salt-Affected Soils - Hiba Shaghaleh; Tahira Akram; Muhammad Zia-ur-Rehman; Muhammad Usman; Yousef Alhaj Hamoud; Muhammad Rizwan; Hesham F. Alharby; Amnah M. Alamri; Basmah M. Alharbi; Awatif M. Abdulmajeed (Journal of Soil Science and Plant Nutrition, 2025)

Distinct nitrogen application strategies and straw incorporation modulate carbon mineralization rate and SOC dynamics by regulating soil microbiome composition - Muhammad Irfan; Yiliu Wang; Solomon Yokamo; Yifan Wang; Muhammad Ahmed Akram; Dianjun Lu; Xiaoqin Chen; Huoyan Wang (Applied Soil Ecology, 2025)

Ex-situ multi-media bioleaching and functional characterization of indigenous fungal strains for chromium and zinc remediation in polluted soils - Ibrar Khan; Muhammad Bilal Akram; Aneela Rehman; Mujaddad Ur Rehman; Tawaf Ali Shah; Saad A. Alamri; Yasser S. Mostafa; Abdulrahman A. Almehizia (Biodegradation, 2025)

Mitigating Fruit Drop Challenges: Unraveling the Role of Plant Growth Regulators and Micronutrients in Jujube (Ziziphus mauritiana L.) cvs. in the Cholistan Desert, Pakistan - Abdul Haseeb Ahmed; Rashad Qadri; Khalid Hussain; Muhammad Tahir Akram; Muhammad Azam; Muhammad Awais Ghani; Muhammad Mumtaz Khan; Muhammad Asif Rai; Basharat Ali; Abd El-Zaher M. A. Mustafa; Mohamed S Elshikh; Ghulam Murtaza; et al. (Applied Fruit Science, 2025)

Development of a Novel Composite Catalyst containing Renewable Biochar blended with Zinc Oxide and Copper Diphenyl Amine for Visible Light Photocatalytic Degradation of Methylene Blue - Muhammad Raashid; Muhammad Zain Akram; Mohsin Kazmi; Kashaf Imran; Amir Ikhlaq; Muhammad Bin Saeed; Naveed Ramzan; Zafar Masood (Water, Air, & Soil Pollution, 2025)

Insights into genetic diversity and chlorpyrifos resistance in fall armyworm Spodoptera frugiperda (Smith) population of Pakistan - Afia Shafique; Muhammad Sarwar; Naima Razzaq; Naveed Akhtar Shad; Saba Akram; Rubab Zahra Naqvi; Muhammad Asif (Phytoparasitica, 2025)

Optimizing Charge Transport Properties of Dithieno[3,2-b:2′,3′-d] Pyrrole-Based Hole Transport Materials for Perovskite Solar Cells: a DFT Study - Nabeel Shahzad; Muhammad Ishaq; Aqsa Laraib; Tazeem Fatima; Rida Fatima; Waqas Akram; Javed Iqbal (Journal of Fluorescence, 2025)

Ultrahigh-porosity peony-like magnesium oxide for the superior adsorption of arsenic (III) and arsenic (V) from aqueous solutions - Ghulam Asghar; Duc Anh Nguyen; Thi Hai Chau Dong; Sumaira Manzoor; Shahid Ali; Muhammad Mansha; Shehzada Muhammad Sajid Jillani; Safyan Akram Khan (Journal of Hazardous Materials, 2025)

Mesozoic Muslim Bagh-Khanozai ophiolite mélange in the western Pakistan: implications for the tectonic evolution of the Neo-Tethys Ocean - Akram Ullah Khan; Yunpeng Dong; Saif Ur Rehman; Bo Hui; Muhmmad Usman; Muhammad Panezai (Journal of Asian Earth Sciences, 2025)

Restoration of alkaline soils contaminated by inorganic elements under pulsed electrokinetics - Abdul Ahad Hussain; Muhammad Moeez; Aasma Akram; Mubashera Ishaq; Kashif Kamran; Muhammad Afzaal; Maryam Hina; Lin Li (Environmental Research, 2025)

Comprehensive ampelographic and biochemical profiling of exotic grapevine (Vitis vinifera L.) cultivars grown under semi-arid conditions - Ubaid Abdul Khaliq; Irfan Ali; Abdel‑Halim Ghazy; Muhammad Tahir Akram; Mahmood-ul-Hassan; Haider Ali; Umer Habib; Tanveer Hussain; Kotb A. Attia; Sajid Fiaz; Abdullah A. Al-Doss; Muhammad Uzair; et al. (Genetic Resources and Crop Evolution, 2025)

Quantitative Analysis of Pesticide Residues in Guava (Psidium guajava L.) Fruit by Using High Performance Liquid Chromatography - Rashad Qadri; Abdul Haseeb Ahmed; Muhammad Umair Ashraf; Muhammad Tahir Akram; Khalid Hussain; Muhammad Azam; Muhammad Imran Khan; Muhammad Mumtaz Khan (Applied Fruit Science, 2025)

Evaluating the Impact of Triacontanol on Physiological, Enzymatic and Biochemical Responses of Psidium Guajava L. Under Salinity Stress - Khalid Hussain; Rashad Qadri; Rashid Iqbal Khan; Abdul Haseeb Ahmed; Muhammad Azam; Muhammad Tahir Akram; Muhammad Imran Khan; Aneeqa Arshad; Swati Shrestha (Applied Fruit Science, 2025)

Predicting ambient PM2.5 levels in the Yangtze River Delta with random forest algorithms: A machine learning approach - Ahmad Hasnain; Muhammad Zaffar Hashmi; Uzair Aslam Bhatti; Basit Nadeem; Geng Wei; Waqas Akram Cheema; Muhammad Asif (Environment, Development and Sustainability, 2025)

Heavy metals removal and reduction of heavy metal phytotoxicity by Arthrobacter, Bacillus, and Pseudomonas strains harboring genes encoding metal resistance - Muhammad Tahir; Muhammad Nasir; Tahir Naqqash; Muhammad Shahid; Abu Bakr Umer Farooq; Muhammad Akram; Muhammad Arshad; Muhammad Kamran; Urooj Khan (Biocatalysis and Agricultural Biotechnology, 2025)

Unlocking Drought Tolerance in Quinoa Varieties: Insights from Biochar-Amended Soil on Root and Stomatal Adaptations - Muhammad Zubair Akram; Fulai Liu; Anna Rita Rivelli; Angela Libutti; Christian Andreasen (Journal of Soil Science and Plant Nutrition, 2025)

Retraction Note: Anti-rheumatic activity of pseudoephedrine (a substituted phenethylamine) in complete Freund’s adjuvant-induced arthritic rats by down regulating IL-1β, IL-6 and TNF-α as well as upregulating IL-4 and IL-10 - Haseeb Ahsan; Hafiz Muhammad Irfan; Alamgeer; Muhammad Shahzad; Mulazim Hussain Asim; Muhammad Akram; Muhammad Shoaib Zafar (Inflammopharmacology, 2025)

Bioactivity of 2-(3,4-Dihydroxyphenyl)-5,7-dihydroxy-2,3-dihydrochromen-4-one from pistacia chinensis on ENPP1 and aldose reductase - Abdur Rauf; Saima Naz; Zuneera Akram; Muhammad Saleem; Taghrid S. Alomar; Najla AlMasoud; Giovanni Ribaudo (Natural Product Research, 2025)

Electrochemical activation of alum sludge for the adsorption of lead (Pb(II)) and arsenic (As): Mechanistic insights and machine learning (ML) analysis - Hye-Bin Kim; Muhammad Fahad Ehsan; Akram N. Alshawabkeh; Jong-Gook Kim (Bioresource Technology, 2025)

Sublethal effect and molecular responses of Musca domestica to cinnamon extracts - Akram Alghamdi; Muhammad Nadir Naqqash; Nimra Batool; Muhammad Asif Farooq; Ahmed Noureldeen; Hadeer Darwish; Attalla F. El-kott; Salama A. Salama; Yasser Rabea Elmarassi (The Science of Nature, 2025)

Jasmonic Acid as a Regulator in Plant Stress Tolerance: Mechanisms and Agricultural Implications - Jalil Ahmad; Faisal Hayat; Ummara Khan; Muhammad Ahsan Altaf; Muhammad Ahmad; Muhammad Tahir Akram; Karthishwaran Kandhan; Mohamed S. Sheteiwy; Juan Li; Mohammed Alyafei (Journal of Crop Health, 2025)

Standardization of Pruning in Dense, High Dense, and Ultra-High Dense Psidium guajava L. Orchards under Drip Irrigation - Mujahid Ali; Malik Muhammad Akram; Asif Iqbal; Muhammad Mohsan; Saqib Ayyub (Applied Fruit Science, 2025)

Structural and functional traits driving Chloris flagellifera proliferation in arid saline environments - Ummar Iqbal; Mansoor Hameed; Farooq Ahmad; Muhammad Sajid Aqeel Ahmad; Khawaja Shafique Ahmad; Ansar Mehmood; Nargis Naz; Muhammad Akram (Acta Physiologiae Plantarum, 2025)

Simultaneous removal of Cr(VI), As(III), and sulfanilamide via an e-barrier electrochemical system: A pilot study - Jong-Gook Kim; Muhammad Fahad Ehsan; Akram N. Alshawabkeh; Kitae Baek (Journal of Hazardous Materials, 2025)

Solvothermal synthesis of ruthenium doped MnV2O7@g-C3N4 nanocomposite for oxygen evolution reaction and high-performance asymmetric supercapacitors - Sidra Aslam; Muhammad Safdar; Sadia Akram; Muhammad Awais; Basharat Ali; Yasir Abbas; Waseem Abbas; Misbah Mirza (Journal of Environmental Chemical Engineering, 2025)

Effects of enzyme supplementation and fermentation in canola-based diets on growth performance, intestinal viscosity and histomorphology in broiler chickens during the finisher phase - Wasim Akram; Abdul Hafeez; Sarzamin Khan; Muhammad Tahir; Rifat Ullah Khan (Tropical Animal Health and Production, 2025)

Microbial Biofortification of Iron in Solanum tuberosum L. through Siderophore-Producing Rhizobacteria along with L-Tryptophan and Iron Sulphate Supply - Zain Mushtaq; Mehwish Liaquat; Sarvet Jehan; Muhammad Tahir Akram; Muhammad Tauseef Jaffar; Abdulrahman Alasmari (Potato Research, 2025)

Development and in vitro tuning of empagliflozin-containing dissolvable microneedle patch for enhanced transdermal delivery - Aqib Javed; Rai Muhammad Sarfraz; Asif Mahmood; Zulcaif Ahmad; Muhammad Rouf Akram; Hira Ijaz; Shammas Ali; Anam Shahzadi (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Globally analysis of production of lactic acid by Lactobacillus plantarum AC11S: kinetics using Mittag-Leffler kernel via mathematical modeling - Muhammad Farman; Aqeel Ahmad; Muhammad Faheem; Kottakkaran Sooppy Nisar; Muhammad Saeed Akram; Hijaz Ahmad (Modeling Earth Systems and Environment, 2025)

Woody Biochar Differently Influences Plant Water Status and Growth of Five Quinoa (Chenopodium Quinoa Willd.) Varieties Under Water Stress - Muhammad Zubair Akram; Angela Libutti; Christian Andreasen; Fulai Liu; Anna Rita Rivelli (Journal of Soil Science and Plant Nutrition, 2025)

Combined Impact of Waste Water and Farm Yard Manure on Growth of Tomato (Solanum lycopersicum L.) and Soil Health: A Sustainable Agriculture Approach - Arsalan Saghir; Muhammad Sohail Akram; Shahzad Ali; Shahla Rashid; Muhammad Ajmal Farhad; Hafiz Muhammad Tayyab Khan; Syed Ayyaz javed; Mohammad Raish; Muhammad Khubaib (Journal of Soil Science and Plant Nutrition, 2025)

Molecular marker based analysis of allelic variation in the spring wheat genome - Hafiz Ghulam Muhu Din Ahmed; Tao Yang; Muhammad Irfan Akram; Rashid Iqbal; Abdullah Ahmed Al-Ghamdi; Dunia A. Al Farraj (Genetic Resources and Crop Evolution, 2025)

PSA level 1 analysis by considering redundancy and diversity of emergency diesel generators for APR-1400 - Muhammad Zubair; Ronak Shahin Radkiany; Mahra Mohammad Aljaradi; Shamma Abdulla Alblooshi; Horeya Sultan Alhammadi; Yumna Akram (Annals of Nuclear Energy, 2025)

Comparison of conventional and process intensified next generation RPB absorbers for decarbonisation of the steel industry - Muhammad Akram; Abdulaziz Gheit; Kris Milkowski; William Gale; Mohamed Pourkashanian (Fuel, 2025)

Integrative taxonomy and multigene phylogeny uncover three novel taxa of the genus Clitopilus from southern Punjab, Pakistan - Muhammad Asif; Malka Saba; Wajahat Akram; Fazli Maula; Fahim Ullah; Momal Batool; Mohsin Ullah; Irmgard Krisai-Greilhuber; Mubashar Raza (Mycological Progress, 2025)

Ethylene precursor, 1-amino cyclopropane-1-carboxylic acid, induced distinct morpho-physio-biochemical improvements to cadmium-stressed mungbean (Vigna radiata L.) - Aneeqa Munawar; Muhammad Tariq Javed; Nudrat Aisha Akram; Sadia Zafar; Muhammad Sohail Akram (South African Journal of Botany, 2025)

Two years monitoring and optimization of a large-scale constructed wetland in the Red Sea designed for 80,000 inhabitants - Muhammad Ishtiaq; Muhammad Akram; Shezhi Tao; Hicham Belmaati; Muhammad Haroon Siyech; Wolfarm Sievert; Alexandros Stefanakis (Journal of Cleaner Production, 2025)

Impact of field evolved resistance on biological parameters of non-targeted Aedes aegypti populations - Nimra Batool; Muhammad Asif Farooq; Waqar Jaleel; Ahmed Noureldeen; Akram Alghamdi; Hadeer Darwish; Naif H. Ashri; Muhammad Nadir Naqqash (Ecotoxicology, 2025)

Genome-wide analysis of CNGC gene family in Brassica juncea (L.) Czern reveals key targets for stress resistance and crop improvement - Akram Ali Baloch; Kaleem U. Kakar; Sumera Rais; Zarqa Nawaz; Abdulwareth A. Almoneafy; Agha Muhammad Raza; Samiullah Khan; Raqeeb Ullah (Plant Gene, 2025)

Role of artificial intelligence in halal authentication and traceability: A concurrent review - Asad Nawaz; Atka Afzal; Ali Khatibi; Amar Shankar; Heena Madan; Hafiza Sana Faisal; Amna Shahbaz; Ifrah Usman; Nimra Zulfiqar; Farhan Saeed; Aftab Ahmed; Ali Imran; et al. (Food Control, 2025)

Burkholderia sp. AQ12-mediated Molecular Adjustments Assist Growth of Salt-stressed Cotton (Gossypium hirsutum L.) By Modulating Biochemical Status and Nutrient Acquisition Patterns - Sidra Batool; Sijal Fatima; Uzma Qaisar; Muhammad Shahid; Muhammad Sohail Akram (Journal of Soil Science and Plant Nutrition, 2025)

RETRACTED ARTICLE: Study of variability, combining ability, genetics and association of different yield related traits in rice (Oryza sativa L.) genotypes - Zeeshan Ali; Muhammad Naeem; Iqra Rafiq; Rao Muhammad Ikram; M. Irfan Akram; Ehab I. Taha; Mounir M. Bekhit; Ozhan Simsek; Tolga Izgu; Temoor Ahmed; Javed Iqbal; Rashid Iqbal (Genetic Resources and Crop Evolution, 2025)

Appraisal of the physio-biochemical efficacy of exogenously applied natural and synthetic sources of plant growth stimulants in modulating drought stress tolerance in maize (Zea mays L.) - Abrar Ahmad; Nudrat Aisha Akram; Muhammad Ashraf (Acta Physiologiae Plantarum, 2025)

Food security in Punjab, Pakistan: rural views on climate disasters and their impacts - Muhammad Usman; Asghar Ali; Sajjad Ahmad Baig; Magdalena Radulescu; Azhar Abbas; Rimsha Akram (Environment, Development and Sustainability, 2025)

Chemically modified filter paper with Jaman fruit extract for visual sensing of milk freshness - Muhammad Naeem Shabbir; Adeel Ahmad; Muhammad Aslam; Ayaz Hassan; Hidayat Ullah; Muhammad Akram; Hafiza Fatima Qayum; Fatima Naeem (Food Chemistry, 2025)

Corrigendum to ‘Trace element bioaccumulation in edible red seaweeds (Rhodophyta): A risk assessment for consumers’ [Environ. Pollut. 307 (2022) 1–10/119560] - Md Solaiman Hossain; Eurida Liyana; Saad Al-din Sifat; Fuad Ameen; Md Akram Ullah; Yeasmin Nahar Jolly; Shamshad Begum Quraishi; Mofazzal Hossain; Sazlina Salleh; Sharmin Akter; Mohammad Afzal Hossain; Muhammad Zobayer Bin Mukhlish; et al. (Environmental Pollution, 2025)

Species sensitivity distributions of microplastics based on toxicity endpoints and particle characteristics: Implications of assessing ecological risk in Tai Lake - Seerat Ul Ain Bhutto; Muhammad Akram; Xue-yi You (Environmental Pollution, 2025)

Intermittent Fasting and Probiotics: Synergistic Modulation of Gut Health for Therapeutic Advantages - Amna Shehbaz; Muhammad Afzaal; Noor Akram; Farhan Saeed; Warda Khan; Faiyaz Ahmed; Aftab Ahmed; Aasma Asghar; Zargham Faisal (Probiotics and Antimicrobial Proteins, 2025)

Disease resistance to tomato yellow leaf curl virus (TYLCV) enhanced by natural plant growth regulators and biopesticide - Sajid Mehmood; Marina Sajid; Tamsal Murtaza; Tanveer Hussain; Rana Naveed Ur Rehman; Muhammad Tahir Akram; Huma Abbas; Khadija Rafiq; Muhammad Kamran; Manzoor Hussain; Muhammad Inam ul Haq; Gull-e-laala Khan (Journal of Plant Diseases and Protection, 2025)

Insight into insecticide resistance mechanism and eco-friendly approaches for the management of olive fruit fly, Bactrocera oleae Rossi: a review - Ansa Majeed; Muhammad Tariq Rasheed; Javairia Akram; Noreen Shahzadi; Mehvish Kousar; Imran Bodlah; Javaid Iqbal; Inzamam Ul Haq; Yasir Munir; Junaid Ali Siddiqui (Journal of Plant Diseases and Protection, 2025)

Evaluation of Genotype × Environment Interaction and Yield Stability of Cotton (Gossypium hirsutum L) Genotypes Under Heat Stress Conditions - Iram Sharif; Saba Aleem; Jamshaid Ali Junaid; Muqadas Aleem; Khazina Jamshaid; Huma Saleem; Muhammad Rizwan; Shahid Munir Chohan; Saqib Sohail; Saba Akram; Muhammad Zeeshan; Ghulam Sarwar (Journal of Crop Health, 2025)

Palyno-anatomical diversity and its implication in the taxonomy of some Plantaginaceae species - Maryam Akram Butt; Nafeesa Zahid; Saraj Bahadur; Sadaf Kayani; Javeed Hussain; Muhammad Zafar (Genetic Resources and Crop Evolution, 2025)

Synergistic anticancer effects of interleukin-21 combined with therapeutic peptides in multiple cancer cells - Muhammad Akram; Nao Akusa Fujimura; Saad Tahir; Rabia Abbas; Mohsin Ahmad Khan; Kausar Malik; Nadeem Ahmed (Biotechnology Letters, 2025)

Simulation and modelling study of a chemical absorption plant to evaluate capture effectiveness when treating high CO2 content iron and steel industry emissions - Jack Wells; Andy Heeley; Muhammad Akram; Kevin J. Hughes; Derek B. Ingham; Mohamed Pourkashanian (Fuel, 2025)

Triangular relation of food processing, nutrition, and osteoarthritis: A solution for the management and prevention of osteoarthritis? - Arashi Shahid; Ammar B. Altemimi; Iahtisham -Ul-Haq; Muhammad Inam-ur-Raheem; Roshina Rabail; Muhammad Hamdan Rashid; Sadia Kafeel; Muhammad Saad Akram; Amin Mousavi Khaneghah; Rana Muhammad Aadil (Food Bioscience, 2024)

Modulation of calcination conditions on the defluorination performance of nano Ce-based adsorbents: The key roles of Ce valence state and oxygen vacancy - Xinyu Yang; Bing Hou; Mingjing Shi; Muhammad Akram; Xinxin Li; Lei Wang; Jingwen Pan (Chemical Engineering Journal, 2024)

Characterisation of the essential oil from Iphiona grantioides and investigation of its antibacterial and antioxidant properties - Shah Iram Niaz; Muhammad Ali; Muhammad Saleem; Rubina Qaisrani; Kamran Safdar; Malik Muhammad Akram; Abdur Rauf; Maqbool Ahmad; Sanaullah Abbasi; Taghrid S. Alomar; Najla AlMasoud; Giovanni Ribaudo (Natural Product Research, 2024)

Exome sequencing in four families with neurodevelopmental disorders: genotype–phenotype correlation and identification of novel disease-causing variants in VPS13B and RELN - Tehseen Ullah Khan Afridi; Ambrin Fatima; Humayoon Shafique Satti; Zaineb Akram; Imran Khan Yousafzai; Wajahat Bin Naeem; Nasreen Fatima; Asmat Ali; Zafar Iqbal; Ayaz Khan; Muhammad Shahzad; Chunyu Liu; et al. (Molecular Genetics and Genomics, 2024)

Movement of amphibians in a habitat mosaic of agriculture landscape - Waseem Ahmed; Muhammad Rais; Ayesha Akram; Muhammad Saeed; Luqman; Sumbul Gill; Aamina Abid; Abdul Hadi (European Journal of Wildlife Research, 2024)

Recombinant expression, downstream optimization, and therapeutic evaluation of recombinant human interleukin-37 for cancer therapy - Zaheer Abbas; Samia Afzal; Nao Akusa Fujimura; Muhammad Akram; Saad Tahir; Kausar Malik; Nadeem Ahmed (Biotechnology Letters, 2024)

Reclamation alters evapotranspiration and its biophysical controls in a meadow grassland on the Mongolian Plateau - Xiaobing Dong; Gang Dong; Jingyan Chen; Tsegaye Gemechu Legesse; Shicheng Jiang; Muhammad Adnan Akram; Lu-Ping Qu; Lulu Wang; Jianming Deng; Changliang Shao (Journal of Environmental Management, 2024)

Unique role of doped Mo into Fe-based catalyst to intensify peroxydisulfate activation for micropollutants degradation: Promote the conversion of SO4•- to FeIV = O - Taozhen Li; Xinyuan Wang; Zihao Fan; Xiaoning Wang; Zhuohang Wu; Muhammad Akram; Lei Wang; Juan Liu; Jingwen Pan; Baoyu Gao (Chemical Engineering Journal, 2024)

RNA interference: a promising biotechnological approach to combat plant pathogens, mechanism and future prospects - Amjad Ali; Muhammad Shahbaz; Fatih Ölmez; Noor Fatima; Ummad Ud Din Umar; Md. Arshad Ali; Muhammad Akram; Jaya Seelan Sathiya Seelan; Faheem Shehzad Baloch (World Journal of Microbiology and Biotechnology, 2024)

Biochemical analysis and fertilization success of Cirrhinus mrigala ova during induced spawning - Shahid Sherzada; Tanveer Ahmad; Saeed Akram Khan; Muhammad Inayat; Sohail Ahmad; Abdur Rahman (Animal Reproduction Science, 2024)

Assessing the electrode configuration in a sandbox system for the removal of sulfanilamide: A pilot study - Jong-Gook Kim; Hye-Bin Kim; Muhammad Fahad Ehsan; Akram N. Alshawabkeh; Kitae Baek (Chemosphere, 2024)

Effective removal of phosphate using La(OH)3@magnetic graphene: A sustainable approach for water remediation - Zahira Bano; Muhammad Akram; Linrui Li; MingZhu Xia; Fengyun Wang (Journal of Environmental Chemical Engineering, 2024)

Architecting high-performance photocatalysts: A review of modified 2D/2D graphene/g-C3N4 heterostructures - Muhammad Yasir Akram; Tuba Ashraf; Lei Tong; Xiulian Yin; Hongjun Dong; Huiling Lu (Journal of Environmental Chemical Engineering, 2024)

Bovine colostrum: Therapeutic potential and clinical evidence - Talha Shireen Khan; Noor Akram; Zargham Faisal; Farhan Saeed; Amara Rasheed; Faiyaz Ahmed; Muhammad Afzaal (International Dairy Journal, 2024)

Deciphering fungicide resistance in Phytophthora: mechanisms, prevalence, and sustainable management approaches - Syed Atif Hasan Naqvi; Muhammad Farhan; Muhammad Ahmad; Rafia Kiran; Noor Fatima; Muhammad Shahbaz; Muhammad Akram; Jaya Seelan Sathiya Seelan; Amjad Ali; Salman Ahmad (World Journal of Microbiology and Biotechnology, 2024)

Genetic Association Among Morpho-Physiological Attributes Against Heat Tolerance in Rice Genotypes - Hafiz Ghulam Muhu-Din Ahmed; Noor Fatima; Yawen Zeng; Muddassir Hussain; Muhammad Moaaz Mushtaq; Ghulam Sabir Hussain; Muhammad Irfan Akram; Amjad Saeed; Adnan Noor Shah; Hayssam M. Ali; Mohamed M. A. Abdelhamid; Sezai Ercisli (Journal of Crop Health, 2024)

Toll-like receptor expression in Pacific white shrimp (Litopenaeus vannamei) reveals differential responses after fungal (Fusarium solani) infection - Yusuf Jibril Habib; Chengjie Yao; Haifu Wan; Jiaming Lin; Hui Ge; Akram Ismael Shehata; Mayada Alhoshy; Muhammad Mohsin; Yilei Wang; Ziping Zhang (Aquaculture International, 2024)

Retraction Note: Assessing the impact of human capital, renewable energy, population growth, economic growth, and climate change policies on achieving the sustainable development goals - Hamza Akram; Jinchao Li; Muhammad Kahlid Anser; Muhammad Irfan; Waqas Ahmad Watto (Environmental Science and Pollution Research, 2024)

Investigation of therapeutic potential of the Il24-p20 fusion protein against breast cancer: an in-silico approach - Shahnila Qureshi; Nadeem Ahmed; Hafiz Muhammad Rehman; Muhammad Imran Amirzada; Fiza Saleem; Kainat Waheed; Afeefa Chaudhry; Iram Kafait; Muhammad Akram; Hamid Bashir (In Silico Pharmacology, 2024)

Correction to: Plant aqueous extracts to Control Tribolium castaneum (Herbst) Infestation during Rice and Wheat storage - Rehana Naseer; Ifra Imtiaz; Sumia Akram; Zainab Liaqat; Irum Liaqat; Muhammad Mushtaq (International Journal of Tropical Insect Science, 2024)

Techno economic and life cycle assessment of olefin production through CO2 hydrogenation within the power-to-X concept - Gabriela A. Cuevas-Castillo; Stavros Michailos; Muhammad Akram; Kevin Hughes; Derek Ingham; Mohamed Pourkashanian (Journal of Cleaner Production, 2024)

Advancing nuclear science education through IRL Integration: A case experiment on criticality mass determination at the Kartini research reactor - Muhammad Zubair; Polina Matesha; Yumna Akram; Prasetyo Haryo Sadewo; Umar Sahiful Hidayat; Argo Satrio Wicaksono; Tri Nugroho Hadi Susanto (Annals of Nuclear Energy, 2024)

Retraction Note: Novel mannich-based derivative of 2-mercaptobenzimidazole (AK7): a new candidate for the treatment of inflammatory arthritis owing to its NF-κB1 inhibitory potential - Gagun Kamran; Hafiz Amir Ali Kharl; Muhammad Nasir Hayat Malik; Waqas Younis; Humaira Nadeem; Aymun Madni Zubair; Muhammad Atif Hayat Malik; Shah Jahan; Ishtiaq Ahmed; Ramla Shabbir; Asma Akram; Irfan Anjum; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

A multiplex PCR assay to detect mislabelling in fish products - Komal; Shahid Sherzada; Muhammad Imran; Saeed Akram Khan; Abdul Wajid (Food Additives & Contaminants Part B-Surveillance, 2024)

In-situ groundwater remediation of contaminant mixture of As(III), Cr(VI), and sulfanilamide via electrochemical degradation/transformation using pyrite - Jong-Gook Kim; Stephanie Sarrouf; Muhammad Fahad Ehsan; Akram N. Alshawabkeh; Kitae Baek (Journal of Hazardous Materials, 2024)

Aflatoxins in the rice production chain: A review on prevalence, detection, and decontamination strategies - Iqra Naeem; Amir Ismail; Muhammad Riaz; Mubashir Aziz; Kashif Akram; Muhammad A. Shahzad; Mavra Ameen; Sher Ali; Carlos A.F. Oliveira (Food Research International, 2024)

Advanced photocatalysis as a viable and sustainable wastewater treatment process: A comprehensive review - Muhammad Ahtasham Iqbal; Sumia Akram; Shahreen khalid; Basant Lal; Sohaib Ul Hassan; Rizwan Ashraf; Gulmira Kezembayeva; Muhammad Mushtaq; Nurzhan Chinibayeva; Ahmad Hosseini-Bandegharaei (Environmental Research, 2024)

Inhibitory potential of Syzygium aromaticum against Fusarium oxysporum f. sp. lycopersici: In-vitro analysis and molecular docking studies - Muhammad Atif; Tehmina Anjum; Ahmad Ali Shahid; Ahmad Hassan; Waheed Akram (South African Journal of Botany, 2024)

Highly efficient nickel recovery from industrial wastewater via synergistic electrodeposition and electrocatalytic oxidation technique - Muhammad Akram; Zahira Bano; Seerat Ul Ain Bhutto; Jingwen Pan; Ahmed Uddin; Muhammad Zaheer Afzal; Linrui Li; Mingzhu Xia; Fengyun Wang (Journal of Environmental Chemical Engineering, 2024)

Evaluation of drought hazards and coping strategies adopted by pastoral communities in the Cholistan Rangeland of Pakistan - Muhammad Farooq Azhar; Muhammad Junaid Faiz; Ehsan Ali; Abida Aziz; Muhammad Akbar; Ghulam Raza; Muhammad Abdullah; Muhammad Muzammil Habib; Muhammad Farooq Akram (Environmental Development, 2024)

Interactive Effect of Drought Stress and l-Methionine on the Growth and Physio-Biochemical Changes in Broccoli (Brassica oleracea L. var. italica): Leaf and Head - Nudrat Aisha Akram; Kaneez Fatima; Haiyan Kong; Nimra Zafar; Seema Mahmood; Muhammad Ashraf; Arafat Abdel Hamed Abdel Latef (Journal of Plant Growth Regulation, 2024)

Enhancement in the safety and reliability of Pressurized Water reactors using Machine Learning approach - Muhammad Zubair; Yumna Akram (Annals of Nuclear Energy, 2024)

Comparative Assessment of Bioactive Compounds, Fruit Quality Attributes and Sugar Profiling in Early Maturing Table Grape (Vitis Vinifera L.) Cultivars from Pothohar, Pakistan - Muhammad Tahir Akram; Rashad Qadri; Muhammad Azam Khan; Arif Atak; Mehwish Liaquat; Tanveer Hussain; Muhammad Mumtaz Khan; Muhammad Azam; Mahmood ul Hasan (Applied Fruit Science, 2024)

Does CPEC benefit the sustainable agricultural development in Pakistan: a comparison with open investment policy 1997 - Nida Akram; Shahla Andleeb; Khalil ur Rehman; Muhammad Waqar Akram; Muhammad Zubair Tariq (Environment, Development and Sustainability, 2024)

Trapping the genetic variation for yield and yield related attributes in bread wheat under water deficit stress - Hafiz Ghulam Muhu-Din Ahmed; Muhammad Naeem; Yawen Zeng; Aziz Ullah; Ghulam Sabir Hussain; Muhammad Irfan Akram; Amjad Saeed; Noor Fatima; Ibtasam Moeez; Hayssam M. Ali; Nagy S. Radwan; Sezai Ercisli; et al. (Euphytica, 2024)

Development of a robust method for Cd(II) ions analysis using CeO2- and CeO2-Cu-BTC-based electrochemical sensors - Sabah Haider; Maria Zaib; Umar Farooq; Muhammad Salman; Rabia Akram Bajwa; Shabnam Shahida; Muhammad Aslam (Environmental Monitoring and Assessment, 2024)

Elucidating the Mechanism of Copper-Induced Photoluminescence Quenching in 2-Phenylbenzimidazole-5-Sulfonic Acid - Muhammad Mubeen; Muhammad Adnan Khalid; Maria Mukhtar; Poshmal Sumreen; Mamoona Tabassum; Shoaib Ashiq; Sheikh Aadil Abbas; Raheel Akram; Azhar Iqbal (Journal of Fluorescence, 2024)

Novel polyamide-hydrazide based reverse osmosis membrane with enhanced antifouling properties - Zhongyang Wang; Muhammad Adnan Akram; Shanshan Zhang; Jingwei Gong; Lihua Zhao; Zhiyu Liu; Q. Jason Niu (Desalination, 2024)

Agro-morphological characterization and genetic variability assessment of soybean [Glycine max (L.) Merr.] germplasm for yield and quality traits - Atta Ullah; Zahid Akram; Ghulam Rasool; Muhammad Waris; Haris Khurshid (Euphytica, 2024)

Plant aqueous extracts to Control Tribolium castaneum (Herbst) Infestation during Rice and Wheat storage - Rehana Naseer; Ifra Imtiaz; Sumia Akram; Zainab Liaqat; Irum Liaqat; Muhammad Mushtaq (International Journal of Tropical Insect Science, 2024)

Retraction Note: Trends of electronic waste pollution and its impact on the global environment and ecosystem - Rida Akram; Natasha; Shah Fahad; Muhammad Zaffar Hashmi; Abdul Wahid; Muhammad Adnan; Muhammad Mubeen; Naeem Khan; Muhammad Ishaq Asif Rehmani; Muhammadd Awais; Mazhar Abbas; Khurram Shahzad; et al. (Environmental Science and Pollution Research, 2024)

Probabilistic risk assessment of microplastics in Tai Lake, China - Seerat Ul Ain Bhutto; Muhammad Akram; Xue-yi You (Science of The Total Environment, 2024)

Zinc and amino acids improve the growth, physiological, and biochemical attributes of corn under different irrigation levels - Ayman M.S. Elshamly; Rashid Iqbal; Baber Ali; Iftikhar Ahmed; Muhammad Irfan Akram; Shehzad Ali; Allah Ditta; Fatih ÇIĞ; Mohamed S. Elshikh; Abd El-Zaher M.A. Mustafa; Mahdy H. Hamed (Rhizosphere, 2024)

Sustainable porous graphene/Co-MOF for the removal of water pollutants: Combined theoretical and experimental studies - Zahira Bano; Muhammad Akram; Naveed Zafar Ali; Muhammad Usman Khan; Fengyun Wang; Linrui Li; Mingzhu Xia (Journal of Water Process Engineering, 2024)

Development and Characterization of Glimepiride-Loaded Polymeric Nanoparticles: Formulation Design and Evaluation - Zaiba Irfan; Muhammad Imran Khan; Muhammad Farhan Sohail; Muhammad Furqan Akhtar; Muhammad Naeem Qaisar; Muhammad Kashif Javed; Fareeha Anwar; Badarqa-tul-Ayesha; Majid Anwar; Aslam Khan; Faizan Akram (Journal of Pharmaceutical Innovation, 2024)

Evaluating the Morpho-physiological Responses of Stevia (Stevia rebaudiana) to Foliar Application of Various Plant Growth Promoters Under Drought Stress - Fatima Ahmadzai; Kanval Shaukat; Hafiz Mohammad Akram; Mahmood ur Rehman Ansari; Noreen Zahra; Abdul Samad; Mereen Nizar; Muhammad Bilal Hafeez; Ali Raza (Journal of Crop Health, 2024)

Effect of experimental boundary conditions and treatment-time on the electro-desalination of soils - Abdul Ahad Hussain; Kashif Kamran; Muhammad Imran; Aasma Akram; Lin Li; Maryam Hina; Muhammad Yasin Naz; Muhammad Shabir Mahr; Athar Mahmood; Abdallah A. A. Mohammed (Environmental Geochemistry and Health, 2024)

Facile green synthesis of Phyllanthus emblica extract based Ag-NPs for antimicrobial and response surface methodology based catalytic reduction applications - Urooj Fatima; Hummera Rafique; Sadia Akram; Season Si Chen; Khalida Naseem; Jawayria Najeeb; Muhammad Tayyab (Journal of Cleaner Production, 2024)

Blockchain technology in a crisis: Advantages, challenges, and lessons learned for enhancing food supply chains during the COVID-19 pandemic - Muhammad Waqar Akram; Nida Akram; Fakhar Shahzad; Khalil Ur Rehman; Shahla Andleeb (Journal of Cleaner Production, 2024)

New insights on designing the next-generation materials for electrochemical synthesis of reactive oxidative species towards efficient and scalable water treatment: A review and perspectives - Amir Taqieddin; Stephanie Sarrouf; Muhammad Fahad Ehsan; Akram N. Alshawabkeh (Journal of Environmental Chemical Engineering, 2023)

Elucidating the Mechanistic Role of Zinc-Lysine to Enhance Cd Tolerance in Diverse Wheat (Triticum aestivum L.) Cultivars Through Distinct Morpho-Physio-Biochemical Improvements Under Cd Stress - Muhammad Hussaan; Saghir Abbas; Qasim Ali; Muhammad Sohail Akram; Kashif Tanwir; Ahmad Raza; Sherjeel Hashmat; Muhammad Aqeel; Hassan Javed Chaudhary; Muhammad Tariq Javed (Journal of Soil Science and Plant Nutrition, 2023)

Expression deregulation of genes related to DNA repair and lead toxicity in occupationally exposed industrial workers - Zertashia Akram; Ishrat Mahjabeen; Mariam Batool; Sana Kanwal; Fatima Nawaz; Mahmood Akhtar Kayani; Muhammad Rizwan (International Archives of Occupational and Environmental Health, 2023)

Impacts of nutritive and bioactive compounds on cancer development and therapy - Sabira Sultana; Abdelhakim Bouyahya; Maksim Rebezov; Mohammad Ali Shariati; Abdelaali Balahbib; Aya Khouchlaa; Ouadie Mohamed El Yaagoubi; Adnan Khaliq; Nasreddine El Omari; Saad Bakrim; Gokhan Zengin; Muhammad Akram; et al. (Critical Reviews in Food Science and Nutrition, 2023)

RETRACTED ARTICLE: Assessing the impact of human capital, renewable energy, population growth, economic growth, and climate change policies on achieving the sustainable development goals - Hamza Akram; Jinchao Li; Muhammad Kahlid Anser; Muhammad Irfan; Waqas Ahmad Watto (Environmental Science and Pollution Research, 2023)

RETRACTED: Variations and driving factors of leaf functional traits in the dominant desert plant species along an environmental gradient in the drylands of China - Muhammad Adnan Akram; Xiaoting Wang; Nawal Shrestha; Yahui Zhang; Ying Sun; Shuran Yao; Jinhui Li; Qingqing Hou; Weigang Hu; Jinzhi Ran; Jianming Deng (Science of The Total Environment, 2023)

Blockchain-enabled smart agriculture: Enhancing data-driven decision making and ensuring food security - Khalil Ur Rehman; Shahla Andleeb; Maryam Ashfaq; Nida Akram; Muhammad Waqar Akram (Journal of Cleaner Production, 2023)

Neutralizing the surging emissions amidst natural resource dependence, eco-innovation, and green energy in G7 countries: Insights for global environmental sustainability - Rabia Akram; Ridwan Lanre Ibrahim; Zhen Wang; Tomiwa Sunday Adebayo; Muhammad Irfan (Journal of Environmental Management, 2023)

Adsorptive Elimination of Rhodamine B Dye by Synthetic Clay-Based Hetero-metallic Oxide Nanocomposite KAB-Ben for Rapid Wastewater Treatment - Asma Raza; Rabia Rehman; Madeeha Batool; Muhammad Muzammil Jahangir; Ayman A. Ghfar; Samjhana Pradhan; Mehwish Akram (Water, Air, & Soil Pollution, 2023)

Design and Evaluation of Continentalic Acid Encapsulated Transfersomal Gel and Profiling of its Anti-arthritis Activity - Muhammad Waseem Akram; Danish Mazhar; Iqra Afzal; Ahmad Zeb; Qurat Ul Ain; Salman Khan; Hussain Ali (AAPS PharmSciTech, 2023)

Viral vectors as carriers of genome-editing reagents - Muhammad Jawad Akbar Awan; Afzal Akram; Imran Amin; Shahid Mansoor (Trends in Plant Science, 2023)

Corrigendum to “Priming of adipose-derived stem cells with curcumin prior to cryopreservation preserves their functional potency: Towards an ‘Off-the-shelf’ therapy for burns” [Cryobiology 110 (2023) 69–78] - Maryam Azam; Hafiz Ghufran; Saba Tasneem; Azra Mehmood; Kausar Malik; Muhammad Amin Yousaf; Moazzam N. Tarar; Shehla Javed Akram; Sheikh Riazuddin (Cryobiology, 2023)

Vector indices and metrological factors associated with dengue fever outbreak in Punjab, Pakistan - Muhammad Irfan Akram; Waseem Akram; Muhammad Asif Qayyoum; Adeela Anwar Rana; Muhammad Yasin; Bushra Saddiq (Environment, Development and Sustainability, 2023)

In-situ hydrogen peroxide formation and persulfate activation over banana peel-derived biochar cathode for electrochemical water treatment in a flow reactor - Jong-Gook Kim; Stephanie Sarrouf; Muhammad Fahad Ehsan; Kitae Baek; Akram N. Alshawabkeh (Chemosphere, 2023)

Microplastics in Tai lake food web: Trophic transfer and human health risk assessment - Seerat Ul Ain Bhutto; Yi-fei Ma; Muhammad Akram; Xue-yi You (Environmental Toxicology and Pharmacology, 2023)

Enhanced soluble expression of active recombinant human interleukin-29 using champion pET SUMO system - Ayesha Munir; Nadeem Ahmed; Muhammad Akram; Nao Akusa Fujimura; Saad Tahir; Kausar Malik (Biotechnology Letters, 2023)

Screening and growth assessment of indigenous and exotic sesame genotypes under osmotic stress - Jahangir Ahmed; Ghulam Qadir; Muhammad Fraz Ali; Talha Javed; Hafiz Muhammad Jhanzab; Fahad Masoud Wattoo; Imran Mahmood; Muhammad Ansar; Muhammad Akram Khan; Usman Zulfiqar; Bilal Ahamad Paray (South African Journal of Botany, 2023)

Assessment of Genetic Damage in Coal Miners of Punjab, Pakistan - Fariha Idrees; Aima Iram Batool; Muhammad Fayyaz ur Rehman; Syed Sikandar Habib; Aksa Akram (Biological Trace Element Research, 2023)

Observing the response of environmental and economic performances to tourism in light of structural changes - Muhammad Wasim Akram; Shuchun Yang; Muhammad Hafeez (Air Quality, Atmosphere & Health, 2023)

Do farmers’ risk perception, adaptation strategies, and their determinants benefit towards climate change? Implications for agriculture sector of Punjab, Pakistan - Muhammad Usman; Asghar Ali; Muhammad Khalid Bashir; Magdalena Radulescu; Khalid Mushtaq; Abdulazeez Hudu Wudil; Sajjad Ahmad Baig; Rimsha Akram (Environmental Science and Pollution Research, 2023)

Eco-friendly microwave assisted sustainable coloration of silk and wool fabric with Acid Blue 07 dye - Shahid Adeel; Hira Akram; Muhammad Usman; Tanveer Hussain Bokhari; Muhammad Aftab; Meral Ozomay (Environmental Science and Pollution Research, 2023)

Performance assessment of gridded climatic data and modeling spatial accuracy ranking matrix for gridded precipitation using a new pixel-based approach: a district-wise case study of Punjab - Muhammad Usman Saleem; Mian Sohail Akram (Arabian Journal of Geosciences, 2023)

Eco-innovation and environmental entrepreneurship: steps towards business growth - Muhammad Wasim Akram; Shuchun Yang; Muhammad Hafeez; Md. Abdul Kaium; Israt Zahan; Raufhon Salahodjaev (Environmental Science and Pollution Research, 2023)

Asian logistics industry efficiency under low carbon environment: policy implications for sustainable development - Muhammad Wasim Akram; Muhammad Hafeez; Shuchun Yang; Narayan Sethi; Shaza Mahar; Raufhon Salahodjaev (Environmental Science and Pollution Research, 2023)

Application of QPPO/PVA based commercial anion exchange membrane as an outstanding adsorbent for the removal of Eosin-B dye from wastewaters - Muhammad Imran Khan; Abdallah Shanableh; Akram M. Alfantazi; Mushtaq Hussain Lashari; Suryyia Manzoor; Ramsha Anwer; Nosheen Farooq; Farid A. Harraz; Mabkhoot Alsaiari; M. Faisal (Chemosphere, 2023)

H2 impact on combustion kinetics, soot formation, and NOx emission of hydrocarbon fuel flames - M. Zuhaib Akram; Fanhua Ma; Muhammad Aziz; Yangbo Deng; Han Wu (Fuel, 2023)

Photocatalytic and Antibacterial Potential of Silver Nanocubes and Nanorods Synthesized via Polyol Reduction Method - Muhammad Zahid Ishaque; Yasir Zaman; Muhammad Shahzad; Abu Bakar Siddique; Sana Shahid; Muhammad Akram; Humaira Kanwal; Muhammad Tahir Akhtar; Safdar Hussain (Water, Air, & Soil Pollution, 2023)

RETRACTED ARTICLE: Novel mannich-based derivative of 2-mercaptobenzimidazole (AK7): a new candidate for the treatment of inflammatory arthritis owing to its NF-κB1 inhibitory potential - Gagun Kamran; Hafiz Amir Ali Kharl; Muhammad Nasir Hayat Malik; Waqas Younis; Humaira Nadeem; Aymun Madni Zubair; Muhammad Atif Hayat Malik; Shah Jahan; Ishtiaq Ahmed; Ramla Shabbir; Asma Akram; Irfan Anjum; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Plant-soil-microbe interactions in maintaining ecosystem stability and coordinated turnover under changing environmental conditions - Muhammad Aqeel; Jinzhi Ran; Weigang Hu; Muhammad Kashif Irshad; Longwei Dong; Muhammad Adnan Akram; Gaber E. Eldesoky; Ahmed Muteb Aljuwayid; Lai Fatt Chuah; Jianming Deng (Chemosphere, 2023)

Priming of adipose-derived stem cells with curcumin prior to cryopreservation preserves their functional potency: Towards an ‘Off-the-shelf’ therapy for burns - Maryam Azam; Hafiz Ghufran; Saba Tasneem; Azra Mehmood; Kausar Malik; Muhammad Amin Yousaf; Moazzam N. Tarar; Shehla Javed Akram; Sheikh Riazuddin (Cryobiology, 2023)

Bombax ceiba flower extract mediated synthesis of Se nanoparticles for antibacterial activity and urea detection - Muhammad Safdar; Sidra Aslam; Misbah Akram; Adnan Khaliq; Samreen Ahsan; Atif Liaqat; Misbah Mirza; Muhammad Waqas; Waseem Akhtar Qureshi (World Journal of Microbiology and Biotechnology, 2023)

Nutritionally rich biochemical profile in essential oil of various Mentha species and their antimicrobial activities - Hina Fazal; Muhammad Akram; Nisar Ahmad; Muhammad Qaisar; Farina Kanwal; Gohar Rehman; Irfan Ullah (Protoplasma, 2023)

Biochar Amendment in Combination with Endophytic Bacteria Stimulates Photosynthetic Activity and Antioxidant Enzymes to Improve Soybean Yield Under Drought Stress - Fahim Nawaz; Rashid Rafeeq; Sadia Majeed; Muhammad Shoaib Ismail; Muhammad Ahsan; Khawaja Shafique Ahmad; Ahsan Akram; Ghulam Haider (Journal of Soil Science and Plant Nutrition, 2023)
The beneficial effects of biochar (BC) and plant growth-promoting bacteria (PGPR) to increase crop yields under harsh environments have been widely reported. However, the knowledge on the synergistic effects of BC and PGPR to induce drought tolerance in oilseeds is scant. In the present study, the effects of cotton sticks derived BC together with PGPR strains ( Paraburkholderia phytofirmans and Bacillus sp.) were examined in water-stressed soybean plants. Initially, the BC application rates (1% and 2%) for soybean were optimized in a pilot experiment (experiment I), and the most effective level (1%) was selected for further studies together with PGPR in the second experiment. The soybean plants were raised in pots under semi-controlled conditions and were subjected to drought stress (25–30% water holding capacity) at pod formation stage. In comparison with control, the drought-mediated decrease in photosynthetic pigments and gas exchange characteristics was markedly lower in BC and PGPR-treated plants. However, the maximum increase in photosynthetic (12–30%) and the enzymatic antioxidant activities (5–20%) was recorded in plants treated with BC + P. phytofirmans , whereas no further significant increase was observed in plants treated with combined BC and Bacillus sp. under water deficit conditions. Similarly, the combined BC and P. phytofirmans application considerably increased the grain yield (14%) under drought stress conditions. We conclude that the combined application of BC + P. phytofirmans could be utilized as an effective strategy to improve soybean yield in dry arid regions.

Staphylococcus Sciuri SAT-17 Facilitated in Vitro Regenerated Sugarcane Plantlets Cultivation in Saline Soil by Harmonizing Oxidative Signaling, Photosynthetic Efficiency and Nutrients Uptake Patterns - Raheel Parvez Abbasi; Muhammad Sohail Akram; Khadija Rafiq; Saadia Basheer; Naeem Iqbal (Journal of Soil Science and Plant Nutrition, 2023)

Fullerenol [60] Nano-cages for Protection of Crops Against Oxidative Stress: A Critical Review - Fahad Shafiq; Muhammad Iqbal; Syed Hammad Raza; Nudrat Aisha Akram; Muhammad Ashraf (Journal of Plant Growth Regulation, 2023)

Modelling wellbeing of farmers by using nexus of climate change risk perception, adaptation strategies, and their drivers on irrigation water in Pakistan - Muhammad Usman; Asghar Ali; Muhammad Khalid Bashir; Sajjad Ahmad Baig; Khalid Mushtaq; Azhar Abbas; Rimsha Akram; Muhammad Shahzad Iqbal (Environmental Science and Pollution Research, 2023)

Tumor micro-environment sensitive release of doxorubicin through chitosan based polymeric nanoparticles: An in-vitro study - Muhammad Usman Akram; Naseem Abbas; Muhammad Farman; Suryyia Manzoor; Muhammad Imran Khan; Sameh M. Osman; Rafael Luque; Abdallah Shanableh (Chemosphere, 2023)

Integrated transcriptomic and metabolomic analysis of Microcystis aeruginosa exposed to artemisinin sustained-release microspheres - Cunhao Du; Wenlu Sang; Chu Xu; Zhiyun Jiang; Jiajia Wang; Yuanyi Fang; Chengjie Zhu; Jakpa Wizi; Muhammad Asif Akram; Lixiao Ni; Shiyin Li (Journal of Hazardous Materials, 2023)

Forage potential of several halophytic species grown on saline soil in arid environments - Hadi Pirasteh-Anosheh; Gholamhassan Ranjbar; Nudrat Aisha Akram; Muhammad Adeel Ghafar; Antonio Panico (Environmental Research, 2023)

Physiological and transcriptome analyses demonstrate the silver nanoparticles mediated alleviation of salt stress in pearl millet (Pennisetum glaucum L) - Imran Khan; Samrah Afzal Awan; Muhammad Rizwan; Muhammad Adnan Akram; Muhammad Zia-ur-Rehman; Xiaosan Wang; Xinquan Zhang; Linkai Huang (Environmental Pollution, 2023)

How do financial fragility and ICT penetration affect renewable energy consumption and green growth in top-polluting economies? - Muhammad Wasim Akram; Danish Ahmed; Anna Trunina; Kashif Hamid; Muhammad Hafeez (Environmental Science and Pollution Research, 2022)

How do energy prices and climate shocks affect human health? Insights from BRICS - Wenxin Wang; Muhammad Hafeez; Hong Jiang; Muhammad Usman Ashraf; Muhammad Asif; Muhammad Wasim Akram (Environmental Science and Pollution Research, 2022)

Nanoparticle’s uptake and translocation mechanisms in plants via seed priming, foliar treatment, and root exposure: a review - Imran Khan; Samrah Afzal Awan; Muhammad Rizwan; Zaid Ul Hassan; Muhammad Adnan Akram; Rezwan Tariq; Marian Brestic; Wengang Xie (Environmental Science and Pollution Research, 2022)

Heterologous expression of cry1Ia12 insecticidal gene in cotton encodes resistance against pink bollworm, Pectinophora gossypiella (Lepidoptera: Gelechiidae); an alternate insecticidal gene for insect pest management - Muhammad Tariq; Bushra Tabassum; Allah Bakhsh; Abdul Munim Farooq; Zahida Qamar; Faheem Akram; Farah Naz; Abdul Qayyum Rao; Kausar Malik; Idrees Ahmad Nasir (Molecular Biology Reports, 2022)

Natural polysaccharide-based biodegradable polymeric platforms for transdermal drug delivery system: a critical analysis - Sobia Noreen; Jin-Xiang Ma; Muhammad Saeed; Fahad Pervaiz; Muhammad Farhan Hanif; Bilal Ahmed; Muhammad Irshad Farooq; Faizan Akram; Muhammad Safdar; Asadullah Madni; Muhammad Naveed; Li Chang-Xing (Drug Delivery and Translational Research, 2022)

Continental‐scale niche differentiation of dominant topsoil archaea in drylands - Weigang Hu; Qingqing Hou; Manuel Delgado‐Baquerizo; James C. Stegen; Qiajun Du; Longwei Dong; Mingfei Ji; Yuan Sun; Shuran Yao; Haiyang Gong; Junlan Xiong; Rui Xia; et al. (Environmental Microbiology, 2022)
Archaea represent a diverse group of microorganisms often associated with extreme environments. However, an integrated understanding of biogeographical patterns of the specialist Haloarchaea and the potential generalist ammonia‐oxidizing archaea (AOA) across large‐scale environmental gradients remains limited. We hypothesize that niche differentiation determines their distinct distributions along environmental gradients. To test the hypothesis, we use a continental‐scale research network including 173 dryland sites across northern China. Our results demonstrate that Haloarchaea and AOA dominate topsoil archaeal communities. As hypothesized, Haloarchaea and AOA show strong niche differentiation associated with two ecosystem types mainly found in China's drylands (i.e. deserts vs. grasslands), and they differ in the degree of habitat specialization. The relative abundance and richness of Haloarchaea are higher in deserts due to specialization to relatively high soil salinity and extreme climates, while those of AOA are greater in grassland soils. Our results further indicate a divergence in ecological processes underlying the segregated distributions of Haloarchaea and AOA. Haloarchaea are governed primarily by environmental‐based processes while the more generalist AOA are assembled mostly via spatial‐based processes. Our findings add to existing knowledge of large‐scale biogeography of topsoil archaea, advancing our predictive understanding on changes in topsoil archaeal communities in a drier world.

Optimization of Process Parameters in Friction Stir Welding of Aluminum 5451 in Marine Applications - Shoaib Ahmed; Rana Atta ur Rahman; Awais Awan; Sajjad Ahmad; Waseem Akram; Muhammad Amjad; Mohd Yazid Yahya; Seyed Saeid Rahimian Koloor (Journal of Marine Science and Engineering, 2022)
Friction stir welding (FSW) is one of the primary fabrication techniques for joining different components, and it has become popular, especially in aluminum alloy structures for marine applications. The welded joint with the friction stir process greatly depends on the process parameters, i.e., feed rate, rotational speed, and pin profile of the tool. In the current study, plates of aluminum 5451 alloy were joined by the FSW technique, and the Taguchi method was used to find the process parameters at an optimal level. The maximum value of tensile strength, i.e., 160.6907 MPa, was achieved using optimum welding conditions of a tool rotation speed of 1400, a feed rate of 18 mm/min, and the tool pin with threads. The maximum value of hardness, i.e., 81.056 HV, was achieved using optimum conditions of 1200 tool rotational speed and a feed rate of 18 mm/min with a tool pin profile having threads. In addition, the contribution in terms of the percentage of each input parameter was found by the analysis of variance (ANOVA). The ANOVA results revealed that the pin profile of the tool has the maximum contribution of 67.77% and 62.42% in achieving the optimum value of tensile strength and hardness, respectively. The study also investigated the joint efficiency of the friction stir welded joint, hardness at the weld zone, and metallography on FSW samples at the optimized level. The effectiveness and reliability of FSW joints for shipping industry applications can be observed by joint efficiency. That was investigated at optimum conditions, and it comes out to be 80.5%.

Deciphering distinct root exudation, ionomics, and physio-biochemical attributes of Serratia marcescens CP-13 inoculated differentially Cd tolerant Zea mays cultivars - Kashif Tanwir; Muhammad Shahid; Saghir Abbas; Qasim Ali; Muhammad Sohail Akram; Hassan Javed Chaudhary; Muhammad Tariq Javed (Environmental Science and Pollution Research, 2022)

A novel lens of stock market capitalization and environmental degradation - Aamir Azeem; Muhammad Akram Naseem; Naveed Ul Hassan; Ijaz Butt; Muhammad Toseef Aslam; Shahid Ali; Atif khan Jadoon (Environmental Science and Pollution Research, 2022)

Toxicity of selected organophosphate and pyrethroid insecticides against larval and adult stages of Culex quinquefasciatus - Muhammad Zubair; Hafiz Azhar Ali Khan; Waseem Akram; Khurram Zia; Rana Muhammad Naeem Ahsan; Malik Muhammad Shahbaz Sharif; Huma Qamar; Muhammad Kamil Malik (International Journal of Tropical Insect Science, 2022)

Therapeutic potential of herbal medicine for the management of hyperlipidemia: latest updates - Abdur Rauf; Muhammad Akram; Hina Anwar; Muhammad Daniyal; Naveed Munir; Sami Bawazeer; Saud Bawazeer; Maksim Rebezov; Abdelhakim Bouyahya; Mohammad Ali Shariati; Muthu Thiruvengadam; Orynzhamal Sarsembenova; et al. (Environmental Science and Pollution Research, 2022)

Habitat characterization of Aedes albopictus - Faisal Hafeez; Unsar Naeem-Ullah; Waseem Akram; Muhammad Arshad; Ayesha Iftikhar; Afifa Naeem; Muhammad Jawad Saleem (International Journal of Tropical Insect Science, 2022)

Caralluma tuberculata exhibits analgesic and anti-arthritic potential by downregulating pro-inflammatory cytokines and attenuating oxidative stress - Syed Ihtisham Haider; Awais Asif; Hafiz Muhammad Farhan Rasheed; Adnan Akram; Qaiser Jabeen (Inflammopharmacology, 2022)

Anticancer properties of medicinal plants and their bioactive compounds against breast cancer: a review on recent investigations - Muhammad Idrees Khan; Abdelhakim Bouyahya; Naoufal E. L. Hachlafi; Naoual El Menyiy; Muhammad Akram; Sabira Sultana; Gokhan Zengin; Lilya Ponomareva; Mohammad Ali Shariati; Oluwafemi Adeleke Ojo; Stefano Dall’Acqua; Tobiloba Christiana Elebiyo (Environmental Science and Pollution Research, 2022)

Development of magnesium oxide@carbon fiber paper composite film for the removal of methyl orange from aqueous phase - Saeed Ahmed; Muhammad Yasir Akram; Ashutosh Kumar; Amit Dhir; Zahid Ali; Sushil Kumar Kansal; Jatinder Kumar Ratan (Nanotechnology for Environmental Engineering, 2022)

Effects of bisphenol a on hematological, serum biochemical, and histopathological biomarkers in bighead carp (Aristichthys nobilis) under long-term exposure - Rabia Akram; Rehana Iqbal; Riaz Hussain; Muhammad Ali (Environmental Science and Pollution Research, 2022)

Investigating the effect of Aspergillus niger inoculated press mud (biofertilizer) on the potential of enhancing maize (Zea mays. L) yield, potassium use efficiency and potassium agronomic efficiency - Urooj Naeem; Irfan ul Haq; Muhammad Afzaal; Akram Qazi; Abdullah Yasar; Amtul bari Tabinda; Yusra Mahfooz; Asad Ullah Naz; Humera Awan (Cereal Research Communications, 2022)

Knowledge, attitude, and practice of clinicians about antimicrobial stewardship and resistance among hospitals of Pakistan: a multicenter cross-sectional study - Sohaib Ashraf; Shoaib Ashraf; Moneeb Ashraf; Muhammad Ahmad Imran; Zawar Ahmad Choudhary; Hadiqa Tul Hafsa; Abeer Bin Awais; Larab Kalsoom; Iqra Farooq; Zaighum Habib; Sidra Ashraf; Qurrat Ul Ain Iqbal; et al. (Environmental Science and Pollution Research, 2022)

Photocatalysis: an effective tool for photodegradation of dyes—a review - Muhammad Saeed; Majid Muneer; Atta ul Haq; Nadia Akram (Environmental Science and Pollution Research, 2022)

Metal-tolerant Pantoea sp. WP-5 and organic manures enhanced root exudation and phytostabilization of cadmium in the rhizosphere of maize - Muhammad Tahir; Muhammad Bismillah Khan; Muhammad Shahid; Iftikhar Ahmad; Umaira Khalid; Muhammad Akram; Ahmad Dawood; Muhammad Kamran (Environmental Science and Pollution Research, 2022)

Transfersomes: a Revolutionary Nanosystem for Efficient Transdermal Drug Delivery - Muhammad Waseem Akram; Humzah Jamshaid; Fiza Ur Rehman; Muhammad Zaeem; Jehan zeb Khan; Ahmad Zeb (AAPS PharmSciTech, 2021)

Strigolactone (GR24) Induced Salinity Tolerance in Sunflower (Helianthus annuus L.) by Ameliorating Morpho-Physiological and Biochemical Attributes Under In Vitro Conditions - Hira Zulfiqar; Muhammad Shahbaz; Muhammad Ahsan; Muhammad Nafees; Hammad Nadeem; Muhammad Akram; Ambreen Maqsood; Sunny Ahmar; Muhammad Kamran; Saud Alamri; Manzer H. Siddiqui; Shah Saud; et al. (Journal of Plant Growth Regulation, 2021)

Venlafaxine demonstrated anti-arthritic activity possibly through down regulation of TNF-α, IL-6, IL-1β, and COX-2 - Mater Hussen Mahnashi; Zeeshan Jabbar; Alamgeer; Hafiz Muhammad Irfan; Mulazim Hussain Asim; Muhammad Akram; Ahmed Saif; Mohammed Abdulrahman Alshahrani; Mohammed Ali Alshehri; Saeed Ahmed Asiri (Inflammopharmacology, 2021)

Comparative efficacy of Ovaprim and hMG (menotropin) to induce breeding in African catfish (Clarias gariepinus) - Muhammad Wajahat Ameer; Farhat Jabeen; Muhammad Asad; Ghazala Kaukab; Amnah Bashir; Misha Rasheed; Hafsa Younis; Naveed Munir; Javaria Nawaz; Rida Zainab; Muhammad Akram (Fish Physiology and Biochemistry, 2021)

Physiopathology and effectiveness of therapeutic vaccines against human papillomavirus - Noor Ayesha; Sara Aboulaghras; Muhammad Jahangeer; Areej Riasat; Rehana Ramzan; Rameen Fatima; Muhammad Akram; Abdelaali Balahbib; Abdelhakim Bouyahya; Ekaterina Sepiashvili; Gokhan Zengin; Mohammad Ali Shariati (Environmental Science and Pollution Research, 2021)

COVID-19 transmission, vulnerability, persistence and nanotherapy: a review - Afzal Husain Khan; Vineet Tirth; Manal Fawzy; Alaa El Din Mahmoud; Nadeem A. Khan; Sirajuddin Ahmed; Syed Sadat Ali; Muhammad Akram; Leena Hameed; Saiful Islam; Gotam Das; Sharmili Roy; et al. (Environmental Chemistry Letters, 2021)

Mitigating Drought Stress in Sunflower (Helianthus annuus L.) Through Exogenous Application of β-Aminobutyric Acid - Allah Wasaya; Tanveer Abbas; Tauqeer Ahmad Yasir; Naeem Sarwar; Ahsan Aziz; Muhammad Mansoor Javaid; Sheeraz Akram (Journal of Soil Science and Plant Nutrition, 2021)

Advances in Salt Tolerance of Some Major Fiber Crops Through Classical and Advanced Biotechnological Tools: A Review - Nudrat Aisha Akram; Fahad Shafiq; Muhammad Ashraf; Muhammad Iqbal; Parvaiz Ahmad (Journal of Plant Growth Regulation, 2021)

Dusky cotton bug Oxycarenus hyalinipennis Costa (Lygaeidae: Hemiptera) loss assessment in cotton - Faisal Hafeez; Muhammad Akram; Muhammad Farooq; Muhammad Saghir; Muhammad Arshad; Ayesha Iftikhar; Afifa Naeem; Unsar Naeem-Ullah (International Journal of Tropical Insect Science, 2021)

RETRACTED ARTICLE: Anti-rheumatic activity of pseudoephedrine (a substituted phenethylamine) in complete Freund’s adjuvant-induced arthritic rats by down regulating IL-1β, IL-6 and TNF-α as well as upregulating IL-4 and IL-10 - Haseeb Ahsan; Hafiz Muhammad Irfan; Alamgeer; Muhammad Shahzad; Mulazim Hussain Asim; Muhammad Akram; Muhammad Shoaib Zafar (Inflammopharmacology, 2021)

Financial development, international trade, and environmental degradation: a nonlinear threshold model based on panel smooth transition regression - Asadullah Khaskheli; Yushi Jiang; Syed Ali Raza; Komal Akram Khan; Muhammad Asif Qureshi (Environmental Science and Pollution Research, 2021)

A missense allele of PEX5 is responsible for the defective import of PTS2 cargo proteins into peroxisomes - Muhammad Ali; Shahid Y. Khan; Tony A. Rodrigues; Tânia Francisco; Xiaodong Jiao; Hang Qi; Firoz Kabir; Bushra Irum; Bushra Rauf; Asma A. Khan; Azra Mehmood; Muhammad Asif Naeem; et al. (Human Genetics, 2021)

Investigating the effect of Aspergillus niger inoculated press mud (biofertilizer) on the potential of enhancing maize (Zea mays L.) yield, phosphorous use efficiency, and phosphorous agronomic efficiency - Urooj Naeem; Muhammad Afzaal; Irfan ul Haq; Akram Qazi; Abdullah Yasar; Amtul Bari Tabinda; Yusra Mahfooz; Asad Ullah Naz; Humera Aslam Awan; Ashfaq Ahmad (Arabian Journal of Geosciences, 2021)

Elucidating Cd-mediated distinct rhizospheric and in planta ionomic and physio-biochemical responses of two contrasting Zea mays L. cultivars - Saghir Abbas; Muhammad Tariq Javed; Qasim Ali; Muhammad Sohail Akram; Kashif Tanwir; Shafaqat Ali; Hassan Javed Chaudhary; Naeem Iqbal (Physiology and Molecular Biology of Plants, 2021)

Lead (Pb)-resistant bacteria inhibit Pb accumulation in dill (Anethum graveolens L.) by improving biochemical, physiological, and antioxidant enzyme response of plants - Akram Rahbari; Hamideh Fatemi; Behrooz Esmaiel Pour; Muhammad Rizwan; Ali-Ashraf Soltani (Environmental Science and Pollution Research, 2021)

Correction to: Effect of Endoxylanase and Iron Oxide Nanoparticles on Performance and Histopathological Features in Broilers - Hamza Rehman; Muzamal Akram; Mubin Mustafa Kiyani; Muhammad Talha Yasin; Abdul Ghani; Javed Iqbal Saggu; Syed Sajid Hussain Shah; Zafar Mahmood Khalid; Syed Ali Imran Bokhari (Biological Trace Element Research, 2021)

Plant growth-promoting Bacillus sp. strain SDA-4 confers Cd tolerance by physio-biochemical improvements, better nutrient acquisition and diminished Cd uptake in Spinacia oleracea L. - Muhammad Shahid; Muhammad Tariq Javed; Kashif Tanwir; Muhammad Sohail Akram; Syeda Khola Tazeen; Muhammad Hamzah Saleem; Sajid Masood; Sadia Mujtaba; Hassan Javed Chaudhary (Physiology and Molecular Biology of Plants, 2020)

Influence of Different Organic Manures and Their Combinations on Productivity and Quality of Bread Wheat - Nauman Ali; Muhammad Naeem Khan; Muhammad Saeed Ashraf; Sobia Ijaz; Hafiz Saeed-ur-Rehman; Muhammad Abdullah; Noor Ahmad; Hafiz Muhammad Akram; Muhammad Farooq (Journal of Soil Science and Plant Nutrition, 2020)

Comparative effects of dietary micro- and nano-scale chitosan on the growth performance, non-specific immunity, and resistance of silver carp Hypophthalmichthys molitrix against Staphylococcus aureus infection - Naima Younus; Amina Zuberi; Tariq Mahmoood; Wasim Akram; Muhammad Ahmad (Aquaculture International, 2020)

First report of apple mosaic virus in peach in Pakistan - Azhar Ul Islam; Muhammad Wahaj Javed; Muhammad Akram; Javed Rahman; Muhammad Tahir; Muhammad Farooq Hussain Munis; Abu Bakr Umer Farooq (Journal of Plant Pathology, 2020)

Chemical fractionation and risk assessment of trace elements in sewage sludge generated from various states of Pakistan - Umair Riaz; Ghulam Murtaza; Saifullah; Muhammad Farooq; Humera Aziz; Ayesha Abdul Qadir; Shahzada Munawar Mehdi; Muhammad Akram Qazi (Environmental Science and Pollution Research, 2020)

Using GIS tools to detect the land use/land cover changes during forty years in Lodhran District of Pakistan - Sajjad Hussain; Muhammad Mubeen; Ashfaq Ahmad; Waseem Akram; Hafiz Mohkum Hammad; Mazhar Ali; Nasir Masood; Asad Amin; Hafiz Umar Farid; Syeda Refat Sultana; Shah Fahad; Depeng Wang; et al. (Environmental Science and Pollution Research, 2020)

Modeling radon time series on the North Anatolian Fault Zone, Turkiye: Fourier transforms and Monte Carlo simulations - Ahmad Muhammad; Fatih Külahcı; Pishtiwan Akram (Natural Hazards, 2020)

Effects of Different Sample Pulverisation Methods on the Extraction of Metabolites from the Fermented Cottonseed Meal Based on UPLC-Q-TOF-MS - Yongqiang Wang; Hongbing Xie; Dongyang Liu; Yimin Wang; Changzhong Liu; Muhammad Akram Khan; Jinqing Jiang; Wenjv Zhang (Current Microbiology, 2020)

Foliage application and seed priming with nitric oxide causes mitigation of salinity-induced metabolic adversaries in broccoli (Brassica oleracea L.) plants - Nudrat Aisha Akram; Naima Hafeez; Muhammad Farid-ul-Haq; Abrar Ahmad; Muhammad Sadiq; Muhammad Ashraf (Acta Physiologiae Plantarum, 2020)

Enhancement of salt tolerance in maize (Zea mays L.) using locally isolated Bacillus sp. SR-2-1/1 - Khadija Rafiq; Muhammad Sohail Akram; Muhammad Shahid; Uzma Qaisar; Naeem Rashid (Biologia, 2020)

Detection and molecular characterization of Clerodendron yellow mosaic virus infecting Volkameria inermis in Pakistan - Afzal Akram; Aqsa Hafeez Khan; Shahid Mansoor; Peter Moffett; Rob W. Briddon; Muhammad Saeed (Journal of Plant Pathology, 2020)

Leading edges in bioremediation technologies for removal of petroleum hydrocarbons - Urooj Naeem; Muhammad Akram Qazi (Environmental Science and Pollution Research, 2020)

Cadmium Partitioning, Physiological and Oxidative Stress Responses in Marigold (Calendula calypso) Grown on Contaminated Soil: Implications for Phytoremediation - Amjad Farooq; Muhammad Nadeem; Ghulam Abbas; Arslan Shabbir; Muhammad Shafique Khalid; Hafiz Muhammad Rashad Javeed; Muhammad Farhan Saeed; Ahsan Akram; Adnan Younis; Gulzar Akhtar (Bulletin of Environmental Contamination and Toxicology, 2020)

Codiaeum variegatum in Pakistan harbours pedilanthus leaf curl virus and papaya leaf curl virus as well as a newly identified betasatellite - Afzal Akram; Aqsa Hafeez Khan; Ghulam Rasool; Shahid Mansoor; Peter Moffett; Rob W. Briddon; Muhammad Saeed (Archives of Virology, 2020)

Determination of oil contents from eight varieties of olea europaea (Olive) grown in Pakistan - Abdul Khaliq; Syed Muhammad Ali Shah; Muhammad Akram; Naveed Munir; Muhammad Daniyal; Muhammad Irshad; Saeed Ahmad (Natural Product Research, 2020)

Arsenic distribution and metabolism genes abundance in Paddy soils from Punjab and Sindh provinces, Pakistan - Muhammad Zaffar Hashmi; Aatika Kanwal; Siwatt Pongpiachan; Xiaomei Su; Wajid Nasim; Mumtaz Ali Saand; Muhammad Mubeen; Rida Akram; Shuhong Wang; Zulkfil Ahmed (Arabian Journal of Geosciences, 2020)

Inanimate surfaces as potential source of 2019-nCoV spread and their disinfection with biocidal agents - Muhammad Zeeshan Akram (VirusDisease, 2020)

Synthesis, characterization, and biocompatibility of lanthanum titanate nanoparticles in albino mice in a sex-specific manner - Irum Naz Akram; Sana Akhtar; Ghulam Khadija; Mian Muhammad Awais; Muhammad Latif; Aasia Noreen; Mehwish Mobeen; Fareeha Sajjad; Zahida Sardar; Shahid Iqbal; Muhammad Naeem Ashiq; Furhan Iqbal (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Inorganic fertilization improves quality and biomass of Moringa oleifera L. - Muhammad Farhan Aslam; Shahzad M. A. Basra; Muhammad Bilal Hafeez; Shahbaz Khan; Sohail Irshad; Shahid Iqbal; Muhammad Sohail Saqqid; Muhammad Zubair Akram (Agroforestry Systems, 2020)

Asymmetric effects of energy efficiency and renewable energy on carbon emissions of BRICS economies: evidence from nonlinear panel autoregressive distributed lag model - Rabia Akram; Muhammad Tariq Majeed; Zeeshan Fareed; Fahad Khalid; Chengang Ye (Environmental Science and Pollution Research, 2020)

Association of intronic polymorphisms (rs1549339, rs13402242) and mRNA expression variations in PSMD1 gene in arsenic-exposed workers - Saqiba Ahmad; Bushra Arif; Zertashia Akram; Malik Waqar Ahmed; Asad Ullah Khan; Muhammad Zahid Hussain; Faisal Rahman; Mahmood Akhtar Kayani; Ishrat Mahjabeen (Environmental Science and Pollution Research, 2020)

GIS-based assessment of aridity over Punjab Province, Pakistan, by using climatic indices - Kanwal Javid; Muhammad Ameer Nawaz Akram; Maria Mumtaz Ranjha; Shazia Pervaiz (Arabian Journal of Geosciences, 2020)

Coagulation- and Adsorption-Based Environmental Impact Assessment and Textile Effluent Treatment - Muhammad Aleem; Jiashun Cao; Chao Li; Haroon Rashid; Yang Wu; Muhammad Imran Nawaz; Muhammad Abbas; Muhammad Waqar Akram (Water, Air, & Soil Pollution, 2020)

Osmoprotection in plants under abiotic stresses: new insights into a classical phenomenon - Faisal Zulfiqar; Nudrat Aisha Akram; Muhammad Ashraf (Planta, 2020)

Awareness and current knowledge of epilepsy - Asmat Ullah Khan; Muhammad Akram; Muhammad Daniyal; Naheed Akhter; Muhammad Riaz; Naheed Akhtar; Mohammad Ali Shariati; Fozia Anjum; Samreen Gul Khan; Abida Parveen; Saeed Ahmad (Metabolic Brain Disease, 2020)

Study of land cover/land use changes using RS and GIS: a case study of Multan district, Pakistan - Sajjad Hussain; Muhammad Mubeen; Waseem Akram; Ashfaq Ahmad; Muhammad Habib-ur-Rahman; Abdul Ghaffar; Asad Amin; Muhammad Awais; Hafiz Umar Farid; Amjad Farooq; Wajid Nasim (Environmental Monitoring and Assessment, 2020)

Assessment of arsenic exposure by drinking well water and associated carcinogenic risk in peri-urban areas of Vehari, Pakistan - Ali Haidar Shah; Muhammad Shahid; Sana Khalid; Natasha; Zunaira Shabbir; Hafiz Faiq Bakhat; Behzad Murtaza; Amjad Farooq; Muhammad Akram; Ghulam Mustafa Shah; Wajid Nasim; Nabeel Khan Niazi (Environmental Geochemistry and Health, 2020)

Citric Acid Functionalized Bougainvillea spectabilis: a Novel, Sustainable, and Cost-effective Biosorbent for Removal of Heavy Metal (Pb2+) from Waste Water - Huma Nazir; Muhammad Salman; Makshoof Athar; Umar Farooq; Abdul Wahab; Momal Akram (Water, Air, & Soil Pollution, 2019)

Alpha-Tocopherol-Induced Regulation of Growth and Metabolism in Plants Under Non-stress and Stress Conditions - Muhammad Sadiq; Nudrat Aisha Akram; Muhammad Ashraf; Fahad Al-Qurainy; Parvaiz Ahmad (Journal of Plant Growth Regulation, 2019)

The effect of lead pollution on nutrient solution pH and concomitant changes in plant physiology of two contrasting Solanum melongena L. cultivars - Muhammad Tariq Javed; Noman Habib; Muhammad Sohail Akram; Qasim Ali; Muhammad Zulqurnain Haider; Kashif Tanwir; Asia Shauket; Hassan Javed Chaudhary (Environmental Science and Pollution Research, 2019)

Identification of two further agriculturally important begomoviruses and their associated satellites infecting the weed Digera arvensis in Pakistan - Afzal Akram; Khalid Pervaiz Akhtar; Najeeb Ullah; Muhammad Qasim Aslam; Peter Moffett; Shahid Mansoor; Rob W. Briddon; Muhammad Saeed (European Journal of Plant Pathology, 2019)

Exogenously applied proline induced changes in key anatomical features and physio-biochemical attributes in water stressed oat (Avena sativa L.) plants - Rehmana Ghafoor; Nudrat Aisha Akram; Muhammad Rashid; Muhammad Ashraf; Muhammad Iqbal; Zhang Lixin (Physiology and Molecular Biology of Plants, 2019)

Thiourea-mediated Nitric Oxide Production Enhances Tolerance to Boron Toxicity by Reducing Oxidative Stress in Bread Wheat (Triticum aestivum L.) and Durum Wheat (Triticum durum Desf.) Plants - Cengiz Kaya; Ali Sarioğlu; Nudrat Aisha Akram; Muhammad Ashraf (Journal of Plant Growth Regulation, 2019)

Identification and analysis of driving factors of CO2 emissions from economic growth in Pakistan - Zubair Akram; Jean Engo; Umair Akram; Muhammad Wasif Zafar (Environmental Science and Pollution Research, 2019)

Oxindole-based chalcones: synthesis and their activity against glycation of proteins - Ayesha Khan; Ajmal Khan; Umar Farooq; Muhammad Taha; Syed Adnan Ali Shah; Sobia Ahsan Halim; Arfa Akram; Mohammed Ziauddin Khan; Abdul Khaliq Jan; Ahmed Al-Harrasi (Medicinal Chemistry Research, 2019)

Trehalose: A Key Organic Osmolyte Effectively Involved in Plant Abiotic Stress Tolerance - Firdos Kosar; Nudrat Aisha Akram; Muhammad Sadiq; Fahad Al-Qurainy; Muhammad Ashraf (Journal of Plant Growth Regulation, 2019)

RETRACTED ARTICLE: Trends of electronic waste pollution and its impact on the global environment and ecosystem - Rida Akram; Natasha; Shah Fahad; Muhammad Zaffar Hashmi; Abdul Wahid; Muhammad Adnan; Muhammad Mubeen; Naeem Khan; Muhammad Ishaq Asif Rehmani; Muhammadd Awais; Mazhar Abbas; Khurram Shahzad; et al. (Environmental Science and Pollution Research, 2019)

Prevalence and current therapy in chronic liver disorders - Muhammad Daniyal; Muhammad Akram; Rida Zainab; Naveed Munir; Aamir Sharif; Syed Muhammad Ali Shah; Bin Liu; Wei Wang (Inflammopharmacology, 2019)

Epibrassinolide Application Regulates Some Key Physio-biochemical Attributes As Well As Oxidative Defense System in Maize Plants Grown Under Saline Stress - Cengiz Kaya; Salih Aydemir; Nudrat Aisha Akram; Muhammad Ashraf (Journal of Plant Growth Regulation, 2018)

Kinetin and Indole Acetic Acid Promote Antioxidant Defense System and Reduce Oxidative Stress in Maize (Zea mays L.) Plants Grown at Boron Toxicity - Cengiz Kaya; Nudrat Aisha Akram; Muhammad Ashraf (Journal of Plant Growth Regulation, 2018)

Redox balance and DNA fragmentation in arsenic-exposed occupational workers from different industries of Pakistan - Maryam Raza; Ishrat Mahjabeen; Muhammad Fahim; Waqar Ahmad Malik; Asad Ullah Khan; Mahmood Akhtar Kayani; Ayesha Khan; Zertashia Akram (Environmental Science and Pollution Research, 2018)

Erosion potential assessment of watersheds through GIS-based hypsometric analysis: a case study of Kurram Tangi Dam - Wasif Yousaf; Syed Ghulam Mohayud-Din-Hashmi; Usman Akram; Urooj Saeed; Sajid Rashid Ahmad; Muhammad Umar; Ambreena Mubashir (Arabian Journal of Geosciences, 2018)

Coal mining trends, approaches, and safety hazards: a brief review - Muhammad Fahad Ullah; Abdullah M. Alamri; Khalid Mehmood; Mian Sohail Akram; Faisal Rehman; Saif Ur Rehman; Omar Riaz (Arabian Journal of Geosciences, 2018)

Oral supplementation of Lanthanum Zirconate nanoparticles moderately affected behavior but drastically disturbed leukocyte count, serum cholesterol levels and antioxidant parameters from vital organs of albino mice in a gender specific manner - Muhammad Nazar Aftab; Irum Naz Akram; Tafheem Khosa; Syeda Qandeel Zahra; Irum Bashir; Muhammad Naeem Ashiq; Furhan Iqbal (Metabolic Brain Disease, 2018)

Molecular characterization and clinical epidemiology of HCV in District Dir (Lower), Pakistan - Sami Ullah; Muhammad Akram Khan; Shafiq Ur Rahman; Imran Khan; Fazal Akbar; Anshu Babbar (VirusDisease, 2018)

Impact of exogenously applied tocopherol on some key physio-biochemical and yield attributes in mungbean [Vigna radiata (L.) Wilczek] under limited irrigation regimes - Muhammad Sadiq; Nudrat Aisha Akram; Muhammad Ashraf (Acta Physiologiae Plantarum, 2018)

Hydrogen sulfide regulates the levels of key metabolites and antioxidant defense system to counteract oxidative stress in pepper (Capsicum annuum L.) plants exposed to high zinc regime - Cengiz Kaya; Muhammad Ashraf; Nudrat Aisha Akram (Environmental Science and Pollution Research, 2018)

Earliness index deters Pectinophora gossypiella incidence on advanced cultivars of Bt cotton - Muhammad Rafiq Shahid; Muhammad Shakeel; Muhammad Farooq; Muhammad Shahid Arain; Chaudhary Muhammad Shahid Hanif; Haichen Yin; Muhammad Akram; Saghir Ahmad (Arthropod-Plant Interactions, 2018)

Aminolevulinic acid and nitric oxide regulate oxidative defense and secondary metabolisms in canola (Brassica napus L.) under drought stress - Nudrat Aisha Akram; Majid Iqbal; Atta Muhammad; Muhammad Ashraf; Fahad Al-Qurainy; Sidra Shafiq (Protoplasma, 2018)

Deciphering the growth, organic acid exudations, and ionic homeostasis of Amaranthus viridis L. and Portulaca oleracea L. under lead chloride stress - Muhammad Tariq Javed; Muhammad Sohail Akram; Noman Habib; Kashif Tanwir; Qasim Ali; Nabeel Khan Niazi; Huma Gul; Naeem Iqbal (Environmental Science and Pollution Research, 2018)

Association of chili leaf curl betasatellite with tomato leaf curl disease - Muhammad Qasim Aslam; Khalid P. Akhtar; Mohy-u-Din Akram; Muhammad Y. Saleem; Nighat Sarwar; Sumaira Yousaf (Journal of General Plant Pathology, 2017)

Antimicrobial and antioxidant activities of a new metabolite from Quercus incana - Farah Gul; Khalid Mohammed Khan; Achyut Adhikari; Salman Zafar; Muhammad Akram; Haroon Khan; Muhammad Saeed (Natural Product Research, 2017)

Phyto-management of Cr-contaminated soils by sunflower hybrids: physiological and biochemical response and metal extractability under Cr stress - Mujahid Farid; Shafaqat Ali; Nudrat Aisha Akram; Muhammad Rizwan; Farhat Abbas; Syed Asad Hussain Bukhari; Rashid Saeed (Environmental Science and Pollution Research, 2017)

Understanding brassinosteroid-regulated mechanisms to improve stress tolerance in plants: a critical review - Fahim Nawaz; Muhammad Naeem; Bilal Zulfiqar; Asim Akram; Muhammad Yasin Ashraf; Muhammad Raheel; Rana Nauman Shabbir; Rai Altaf Hussain; Irfan Anwar; Muhammad Aurangzaib (Environmental Science and Pollution Research, 2017)

Environment polluting conventional chemical control compared to an environmentally friendly IPM approach for control of diamondback moth, Plutella xylostella (L.), in China: a review - Muhammad Shakeel; Muhammad Farooq; Wajid Nasim; Waseem Akram; Fawad Zafar Ahmad Khan; Waqar Jaleel; Xun Zhu; Haichen Yin; Shuzhong Li; Shah Fahad; Saddam Hussain; Bhagirath Singh Chauhan; et al. (Environmental Science and Pollution Research, 2017)

Exogenous application of urea and a urease inhibitor improves drought stress tolerance in maize (Zea mays L.) - Wei Gou; Pufan Zheng; Li Tian; Mei Gao; Lixin Zhang; Nudrat Aisha Akram; Muhammad Ashraf (Journal of Plant Research, 2017)

Identification of a novel copper-activated and halide-tolerant laccase in Geobacillus thermopakistaniensis - Saadia Basheer; Naeem Rashid; Raza Ashraf; Muhammad Sohail Akram; Masood Ahmed Siddiqui; Tadayuki Imanaka; Muhammad Akhtar (Extremophiles, 2017)

Promotive role of 5-aminolevulinic acid on chromium-induced morphological, photosynthetic, and oxidative changes in cauliflower (Brassica oleracea botrytis L.) - Rehan Ahmad; Shafaqat Ali; Fakhir Hannan; Muhammad Rizwan; Muhammad Iqbal; Zaidul Hassan; Nudrat Aisha Akram; Saliha Maqbool; Farhat Abbas (Environmental Science and Pollution Research, 2017)

Exogenous triacontanol-mediated increase in phenolics, proline, activity of nitrate reductase, and shoot k+ confers salt tolerance in maize (Zea mays L.) - Shagufta Perveen; Muhammad Iqbal; Abida Parveen; Muhammad Sohail Akram; Muhammad Shahbaz; Shehnal Akber; Aneeqa Mehboob (Brazilian Journal of Botany, 2017)

Optimizing the phosphorus use in cotton by using CSM-CROPGRO-cotton model for semi-arid climate of Vehari-Punjab, Pakistan - Asad Amin; Wajid Nasim; Muhammad Mubeen; Muhammad Nadeem; Liaqat Ali; Hafiz Mohkum Hammad; Syeda Refat Sultana; Khawar Jabran; M. Habib ur Rehman; Shakeel Ahmad; Muhammad Awais; Atta Rasool; et al. (Environmental Science and Pollution Research, 2017)

Worldwide Status of Fresh Fruits Irradiation and Concerns about Quality, Safety, and Consumer Acceptance - Hafiz Muhammad Shahbaz; Kashif Akram; Jae-Jun Ahn; Joong-Ho Kwon (Critical Reviews in Food Science and Nutrition, 2016)

Complete genome sequencing and comparative analysis of three dengue virus type 2 Pakistani isolates - Madiha Akram; Muhammad Idrees (VirusDisease, 2016)

Trehalose pretreatment induces drought tolerance in radish (Raphanus sativus L.) plants: some key physio-biochemical traits - Nudrat Aisha Akram; Muhammad Waseem; Rabia Ameen; Muhammad Ashraf (Acta Physiologiae Plantarum, 2016)

Efficacy of silicon priming and fertigation to modulate seedling’s vigor and ion homeostasis of wheat (Triticum aestivum L.) under saline environment - Muhammad Azeem; Naeem Iqbal; Shakila Kausar; M. Tariq Javed; M. Sohail Akram; M. Asim Sajid (Environmental Science and Pollution Research, 2015)

Exogenous application of trehalose alters growth, physiology and nutrient composition in radish (Raphanus sativus L.) plants under water-deficit conditions - Nudrat Aisha Akram; Sidra Noreen; Tabassum Noreen; Muhammad Ashraf (Brazilian Journal of Botany, 2015)

Genetics and mechanism of resistance to deltamethrin in the house fly, Musca domestica L., from Pakistan - Hafiz Azhar Ali Khan; Waseem Akram; Muhammad Saleem Haider (Ecotoxicology, 2015)

Evaluating pasture and soil allowance of manganese for Kajli rams grazing in semi-arid environment - Zafar Iqbal Khan; Kafeel Ahmad; Muhammad Ashraf; Syed Ali Hassan Naqvi; Alireza Seidavi; Nudrat Aisha Akram; Vito Laudadio; Vincenzo Tufarelli (Tropical Animal Health and Production, 2015)

Synergistic effects of drought and ascorbic acid on growth, mineral nutrients and oxidative defense system in canola (Brassica napus L.) plants - Sidra Shafiq; Nudrat Aisha Akram; Muhammad Ashraf; Amara Arshad (Acta Physiologiae Plantarum, 2014)

Citric Acid Cycle and Role of its Intermediates in Metabolism - Muhammad Akram (Cell Biochemistry and Biophysics, 2014)

Distinctive microRNA expression signatures in proton-irradiated mice - Shahid Yar Khan; Muhammad Akram Tariq; James Patrick Perrott; Christopher Drew Brumbaugh; Hyunsung John Kim; Muhammad Imran Shabbir; Govindarajan T. Ramesh; Nader Pourmand (Molecular and Cellular Biochemistry, 2013)

Minireview on Achillea millefolium Linn - Muhammad Akram (The Journal of Membrane Biology, 2013)

Regulation in Plant Stress Tolerance by a Potential Plant Growth Regulator, 5-Aminolevulinic Acid - Nudrat Aisha Akram; Muhammad Ashraf (Journal of Plant Growth Regulation, 2013)

Aflatoxin contamination in different fractions of rice from Pakistan and estimation of dietary intakes - Shahzad Z. Iqbal; Muhammad R. Asi; Agustin Ariño; Noreen Akram; Muhammad Zuber (Mycotoxin Research, 2012)

A Study on the Transfer of Iron in Soil–Plant–Animal Continuum Under Semi-arid Environmental Conditions in Sargodha, Pakistan - Zafar Iqbal Khan; Muhammad Ashraf; Muhammad Khalid Mukhtar; Nasra Raza; Kafeel Ahmad; Nudrat Aisha Akram (Biological Trace Element Research, 2011)

A Study on the Transfer of Cadmium from Soil to Pasture Under Semi-Arid Conditions in Sargodha, Pakistan - Zafar Iqbal Khan; Muhammad Ashraf; Kafeel Ahmad; Nudrat Aisha Akram (Biological Trace Element Research, 2011)

Salt-induced modulation in growth, photosynthetic capacity, proline content and ion accumulation in sunflower (Helianthus annuus L.) - Muhammad Shahbaz; Muhammad Ashraf; Nudrat Aisha Akram; Asma Hanif; Shumaila Hameed; Sundus Joham; Rehana Rehman (Acta Physiologiae Plantarum, 2011)

Erratum to: The effect of acute dose charge particle radiation on expression of DNA repair genes in mice - Muhammad Akram Tariq; Ayodotun Soedipe; Govindarajan T. Ramesh; Honglu Wu; Ye Zhang; Shishir Shishodia; Daila S. Gridley; Nader Pourmand; Olufisayo Jejelowo (Molecular and Cellular Biochemistry, 2011)

The effect of acute dose charge particle radiation on expression of DNA repair genes in mice - Muhammad Akram Tariq; Ayodotun Soedipe; Govindarajan Ramesh; Honglu Wu; Ye Zhang; Shishir Shishodia; Nader Pourmand; Olufisayo Jejelowo (Molecular and Cellular Biochemistry, 2011)

Determination of Boron Contents in Water Samples Collected from the Neelum valley, Azad Kashmir, Pakistan - Muhammad Akram; Matiullah; Arshid Iqbal; S. N. Husaini; Fariha Malik (Biological Trace Element Research, 2011)

Prospectus of growing barley and mustard with saline groundwater irrigation in fine‐ and coarse‐textured soils of Cholistan desert - Muhammad Akram Kahlown; Muhammad Akram; Zamir Ahmed Soomro; W. D. Kemper (Irrigation and Drainage, 2009)
The groundwater in Pakistani sandy deserts is generally highly saline and not suitable for drinking. However, it can be utilized for growing beneficial salt‐tolerant plants. To explore the potential of desert land for farm production two crops of barley and mustard were cultivated on coarse‐ and fine‐textured soils with saline water irrigations in the Cholistan desert. The salinity (electrical conductivity, EC) of irrigation water was 6.2 dS m −1 . The barley and mustard crops were irrigated five and four times, respectively, including pre‐sowing irrigation. At the end of crop maturity, as a result of saline water irrigation the soil infiltration was reduced by an average of 7.0%. The EC and exchangeable sodium percentage (ESP) of the experimental plots were increased by 2.2 dS m −1 and 9.0, respectively. The average yield of barley and mustard was 264 and 177 kg ha −1 respectively. It was concluded that production of barley and mustard crops could be increased further by better levelling the plots, reducing level differences to less than 10 cm. The saline water should be used carefully to irrigate fine‐textured soils to keep the salinity within the safe limit to avoid permanent failure of crop growth and yield. Copyright © 2008 John Wiley & Sons, Ltd.

Simple mathematical model for optimisation of rainwater storage reservoirs in the Cholistan desert - Muhammad Akram Kahlown; Abdul Majeed (Irrigation and Drainage, 2008)
The cost of constructing storage reservoirs in Cholistan was studied using a mathematical model. The variables studied were reservoir side slope and depth, seepage, evaporation and capacity of the reservoir. After computing the reservoir dimensions to store the required 15 140 m 3 , a full reservoir was assumed starting from 1 August of the year. The depth and quantity of water stored were then depleted by use, evaporation and seepage by the month. In this manner, the length of time that water would be available was computed. The study showed that under general conditions a 3 m deep reservoir would be depleted by December or January, a 4.6 m deep reservoir would be depleted by March or April and a 6 m deep reservoir would be depleted by April or May. Only a 7.6 or 9 m deep reservoir would contain water for a whole year provided that both seepage and evaporation are controlled. The recommended reservoir dimensions are 6 m deep with 1 : 2 or 1 : 3 side slopes, as these give minimum cost plus better water availability. The cost with the recommended optimal dimension was US$6 per m 3 with good seepage and evaporation control. Copyright © 2008 John Wiley & Sons, Ltd.

Design, construction and performance evaluation of small tile drainage systems in the Indus Basin - Muhammad Akram Kahlown; Muhammad Khan Marri; Muhammad Azam (Irrigation and Drainage, 2007)

Factors affecting success and failure of trickle irrigation systems in Balochistan, Pakistan - Muhammad Akram Kahlown; William Doral Kemper (Irrigation Science, 2007)

Individual and combined effect of waterlogging and salinity on crop yields in the Indus basin - Muhammad Akram Kahlown; Muhammad Azam (Irrigation and Drainage, 2002)
Waterlogging and salinity are the major threats to the sustainability of irrigated agriculture in Pakistan. About 50% of the Culturable Command Area (CCA) in the Fordwah Eastern Sadiqia South (FESS) is affected by waterlogging and 12% by surface and profile salinity. A sample of 26 watercourses was selected in the project area to evaluate the individual and combined impacts of waterlogging and salinity on the yields of cotton, wheat, sugarcane and rice. The crop yields were measured separately for waterlogged fields and those affected with salinity and waterlogging simultaneously. The extent of yield loss as result of a rise in the water table from 1–2 m to less than 1 m was 27 and 33% for wheat and sugarcane crops, whereas it was 7 and 6% in the case of a drop of the water table to more than 2 m. For cotton, a rising water table from 2–3 m to 1–2 m and less than 1 m gave a yield decrease of about 11 and 60% respectively. The rice crop preferred waterlogging, and in contrast to other crops, gave about 7% less yield with a lowering of the water table from less than 1 m to 1–2 m. The wheat and sugarcane yields had decreasing trends with salinity in excess of 4 dS m −1 and had complete failures with salinity greater than 12 dS m −1 at water table depths of less than 1, 1–2 and 2–3 m. The cotton crop demonstrated relatively higher salinity tolerance under a water table deeper than 1 m. However, this crop could not survive at salinity levels in excess of 12 dS m −1 at water table depth of less than 1 m. The rice crop was a complete failure at salinity level of greater than 12 dS m −1 under water table depths of less than 1 and 1–2 m. The combined impact of waterlogging and salinity was more harmful to crop yields when compared with the individual effects of waterlogging. The combined analysis of waterlogging and salinity on crop yields provide a good sensitivity of the salinity‐yield relationships and indicated the importance of subsurface drainage. Copyright © 2002 John Wiley & Sons, Ltd.